Novel metal-silicon alloy-carbon compound, electrode and device

By melting lithium alloy into particles containing silicon and porous carbon brackets, the low Coulomb efficiency and lithium dendrites growth problems of lithium metal anode in lithium-ion batteries are solved, and higher battery performance and longer cycle life are achieved.

CN119422258APending Publication Date: 2025-02-11GROUP14 TECHNOLOGIES INC +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380047664.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-02
Filing Date
2023-05-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The application of lithium metal anode in lithium-ion batteries is limited by its low Coulomb efficiency and lithium dendrites growth, resulting in poor battery performance, limited cycle life and safety issues.

Method used

By alloying lithium into particles containing silicon and porous carbon scaffolds, the porous carbon scaffold provides nucleation sites and shape limitations, inhibits the growth of lithium dendrites, and improves the electrochemical properties of lithium.

Benefits of technology

Improved first-time cycle efficiency, Coulomb efficiency and cycle stability are achieved, the weight and volume energy density of lithium-ion batteries are improved, and the sensitivity to lithium dendrites is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119422258A_ABST
    Figure CN119422258A_ABST
Patent Text Reader

Abstract

The present disclosure relates to particulate lithium-silicon alloy-carbon composites and methods of manufacture thereof, as well as their corresponding devices and their corresponding methods of manufacture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to novel composites containing metals, particularly wherein the novel composites contain particles containing Group 14 elements (e.g., carbon and silicon), wherein the silicon contains various domains such as elemental silicon, silicon-metal alloys, and combinations thereof. Optionally, the composites may also contain domains of alloy metals in non-alloy form. The metal contained in the metal-silicon alloy domains may be aluminum, germanium, tin, lithium, or a combination thereof. In a preferred embodiment, the metal is lithium. These materials are produced by providing a novel method for introducing silicon, lithium-silicon alloys, and combinations thereof into the pores of porous carbon scaffold particles. Optionally, the metal, particularly lithium, may also contain non-alloy domains, such as metal domains. The porous carbon scaffold particles may be produced from various precursors as known in the art. Such carbon precursors include, but are not limited to, cellulose, lignin, lignocellulosic materials, sugars and polyols, organic acids, phenolic compounds, crosslinking agents and amine compounds, and combinations thereof. The metal alloyed in the silicon within the porous scaffold may be provided in metallic form, or alternatively, a metal salt or other metal-containing substance may be used as a precursor for the metal within the metal-silicon alloy-carbon composite. Suitable porous scaffolds include, but are not limited to, porous carbon scaffolds, such as carbon having a pore volume comprising micropores (less than 2 nm), mesopores (2 nm to 50 nm), and / or macropores (greater than 50 nm). Background Art

[0002] Lithium is a potentially useful anode material due to its high specific capacity (3900 mAh / g), low redox potential (-3.04 V), and ability to provide the entire lithium supply to the battery (e.g., enabling battery chemistries with lithium-free cathode materials). However, the practical application of lithium metal anodes is still limited by their low coulombic efficiency (CE) and the growth of lithium dendrites during lithium dissolution / deposition. This tendency for lithium stripping and plating degrades battery performance, leading to limited cycle life and serious safety issues, which hinders the practical application of batteries with lithium metal in the anode.

[0003] To address these issues, there has been some limited progress in “pre-lithiation”, also referred to in some literature as “pre-doping of lithium ions”, to add lithium to the active lithium content of lithium-ion batteries (LIBs) prior to battery cell operation (F Holtstiege, P R M Winter, and T Placke, “Pre-Lithiation Strategies for Rechargeable Energy Storage Technologies: Concepts, Promises and Challenges,” Batteries 2018, 4(1), 4). This approach can provide limited improvements, such as increased reversible capacity and, therefore, higher gravimetric or volumetric energy density. It is important to note that in this context, pre-lithiation is performed on the device, particularly on an anode electrode comprising a silicon-containing anode active material. Although some progress has been made, significant barriers to the commercial deployment of pre-lithiation remain in terms of increased battery costs and increased battery manufacturing complexity, and therefore, large-scale application of pre-lithiation technology to battery manufacturing remains difficult. Fundamentally, electrode-level pre-lithiation has commercial barriers that require battery manufacturers to scale up and install additional significant equipment.

[0004] The present disclosure overcomes these problems by providing a particle that alloys a metal (particularly lithium) into a silicon and porous carbon scaffold. The particles are granular; in a preferred embodiment, the resulting lithium-silicon alloy-carbon composite particles are stable under ambient conditions, or alternatively, are stable under conditions that have been used for commercial electrode (e.g., cathode electrode) and battery manufacturing. Therefore, the novel lithium-silicon alloy-carbon composite particle materials disclosed herein can be integrated into existing commercial processes, thereby achieving easy scale-up and adoption into existing electrode and battery production lines to promote commercial applications. Summary of the invention

[0005] The present disclosure relates to compositions and methods for making novel metal-Group 14 composite materials, as well as electrodes and batteries comprising the compositions. The metal-Group 14 composite material may be a metal-silicon-carbon composite material, such as a metal-silicon alloy-carbon composite material, such as a lithium-silicon alloy-carbon composite material. The material may be granular, such as by producing porous carbon scaffold particles, followed by impregnation of silicon, and then impregnation of metal (particularly lithium) into one or more pores of the porous carbon scaffold particles. To this end, the introduction of lithium may be achieved by various methods, including but not limited to melt intrusion, electrochemical deposition, electrode reduction, chemical reduction, lithium evaporation, or a combination thereof. In certain embodiments, lithium exists in the form of an alloy formed with silicon in one or more pores of a porous carbon scaffold. In some embodiments, the metal-Group 14 composite particles may include an outer layer composed of carbon or other inorganic substances. In some embodiments, the metal-lithium alloy-carbon composite is produced by heat treating a mixture of carbon and lithium precursor materials.

[0006] The domain size of the impregnated lithium can vary, for example, the impregnated lithium domains can reflect the size of the silicon located within the pores of the porous carbon support, for example, can be less than 0.5nm, or 0.5nm to 1nm, or less than 1nm, or 1nm to 2nm, or less than 2nm, or 2nm to 4nm, or less than 4nm, or less than 5nm, or less than 10nm, or 2nm to 50nm, or less than 50nm, or greater than 50nm, or a combination thereof. The porous carbon support can be a granular porous carbon, and the average particle size can be 100nm to 100um.

[0007] A key advantage of impregnating lithium into silicon in the pores of a porous carbon support is that the carbon provides nucleation sites for impregnating lithium while dictating the shape and size of the largest particles. Another advantage of impregnating lithium into silicon in the pores of a porous carbon support is that the composite particles can retain residual intra-particle voids, which can provide further electrochemical benefits for the lithium-silicon alloy-carbon composite anode materials disclosed herein. Another advantage of confining the growth of lithium in the anode within the nanoporous structure is reduced sensitivity to lithium dendrite formation or electroplating. In addition, the metal-lithium alloy-carbon composite structure promotes the nano-sized lithium in the anode to retain lithium in an amorphous phase.

[0008] This property provides improved first cycle efficiency (FCE) (which in turn leads to lower requirements for the cathode and therefore higher gravimetric and volumetric battery energy densities), improved coulombic efficiency (CE), and improved cycling stability combined with high charge / discharge rates (particularly combined with the proximity of lithium within the silicon within the conductive carbon scaffold).

[0009] Such lithium-silicon alloy-carbon composite materials as disclosed herein have utility as battery materials, for example, as anode active materials for conventional or solid-state lithium-ion batteries. Such lithium-silicon alloy-carbon composite materials as disclosed herein have utility as battery materials, for example, as anode materials in lithium-silicon batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 .X-ray diffraction patterns of various composite materials.

[0011] Figure 2 .X-ray diffraction pattern of lithium-alloyed silicon-carbon composite.

[0012] Figure 3 .Graphs of the electrochemical charge / discharge cycle stability of various composite materials. DETAILED DESCRIPTION

[0013] In the following description, certain specific details are set forth to provide a thorough understanding of various embodiments. However, those skilled in the art will appreciate that the present disclosure may be practiced without these details. In other cases, well-known structures are not shown or described in detail to avoid unnecessarily obscuring the description of the embodiments. Unless the context otherwise requires, throughout the specification and claims, the words "comprise" and variations thereof, such as "comprises" and "comprising" should be interpreted as open, inclusive meanings, i.e., "including, but not limited to". In addition, the titles provided herein are merely for convenience and do not explain the scope or meaning of the disclosure claimed.

[0014] Reference to "one embodiment" or "embodiment" throughout the specification means that the specific features, structures or characteristics described in conjunction with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" that appear in various places throughout the specification do not necessarily all refer to the same embodiment. In addition, in one or more embodiments, specific features, structures or characteristics can be combined in any suitable manner. In addition, as used in this specification and the appended claims, the singular forms "one / a kind (a)", "an" and "the" include plural indicators unless the content clearly indicates otherwise. It should also be noted that the term "or" is generally used in its sense of including "and / or", unless the content clearly indicates otherwise.

[0015] A. Porous Scaffold Materials

[0016] For the purpose of the embodiments of the present disclosure, a porous support can be used, and lithium will be impregnated therein. In this article, the porous support can include various materials. In some embodiments, the porous support material mainly comprises carbon, such as hard carbon. Other allotropes of carbon, such as graphite, amorphous carbon, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene and / or carbon fiber are also conceivable in other embodiments. Porosity can be introduced into the carbon material in various ways. For example, the porosity in the carbon material can be achieved by adjusting the polymer precursor and / or processing conditions to produce the porous carbon material, and is described in detail in subsequent chapters.

[0017] In other embodiments, the porous support comprises a polymer material. For this reason, it is foreseeable that a variety of polymers have practicality in various embodiments, including but not limited to inorganic polymers, organic polymers and other polymers. Examples of organic polymers include but are not limited to sulfur-containing polymers (such as polysulfides and polysulfones), low-density polyethylene (LDPE), high-density polyethylene (HDPE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), nylon, nylon 6, nylon 6,6, Teflon (polytetrafluoroethylene), thermoplastic polyurethane (TPU), polyurea, poly (lactide), poly (glycolide) and combinations thereof, phenolic resins, polyamides, polyaramides, polyethylene terephthalate, polychloroprene, polyacrylonitrile, polyaniline, polyimide, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PDOT:PSS) and other substances known in the art. Organic polymers can be synthetic or natural sources. In some embodiments, the polymer is a polysaccharide, such as sucrose, starch, cellulose, cellobiose, amylose, amylopectin, gum arabic, lignin, etc. In some embodiments, the polysaccharide is derived from the caramelization of monosaccharides or oligosaccharides (e.g., fructose, glucose, sucrose, maltose, raffinose, etc.).

[0018] In certain embodiments, the porous scaffold polymer material comprises a coordination polymer. Coordination polymers herein include but are not limited to metal organic frameworks (MOFs). The techniques for producing MOFs and exemplary types of MOFs are known and documented in the art ("The Chemistry and Applications of Metal-Organic Frameworks, Hiroyasu Furukawa et al. Science 341, (2013); DOI: 10.1126 / science.1230444). Examples of MOFs in the context include but are not limited to Basolite TM Materials and zeolitic imidazolate frameworks (ZIFs).

[0019] With the myriad of polymers envisioned as potentially providing porous substrates, various processing methods are envisioned in various embodiments to achieve the porosity. In this context, as is known in the art, the general methods for imparting porosity to various materials are myriad, including, but certainly not limited to, methods involving emulsification, micellization, gasification, dissolution followed by solvent removal (e.g., freeze drying), axial compaction and sintering, gravity sintering, powder rolling and sintering, static pressing and sintering, metal spraying, metal coating and sintering, metal injection molding and sintering, and the like. Other methods of producing porous polymer materials are also envisioned, including the production of porous gels, such as freeze-dried gels, aerogels, and the like.

[0020] In certain embodiments, the porous scaffold material comprises a porous ceramic material. In certain embodiments, the porous scaffold material comprises a porous ceramic foam. In this article, as known in the art, the general method for imparting porosity to ceramic materials is different, including but certainly not limited to creating porous. In this article, the general method and materials suitable for comprising porous ceramics include but are not limited to porous alumina, porous zirconia toughened alumina, porous partially stabilized zirconia, porous alumina, porous sintered silicon carbide, sintered silicon nitride, porous cordierite, porous zirconia, clay-bonded silicon carbide, etc.

[0021] In certain embodiments, porous material includes porous metal. In this respect, suitable metal includes but is not limited to porous aluminum, porous steel, porous nickel, porous high nickel alloy (Inconcel), porous Hastelloy, porous titanium, porous copper, porous brass, porous gold, porous silver, porous germanium and other metals known in the art that can form porous structures. In some embodiments, porous support material includes porous metal foam. The type of metal and the manufacturing method associated therewith are known in the art. This method includes but is not limited to casting (including foaming, infiltration and lost foam casting), deposition (chemistry and physics), gas eutectic formation and powder metallurgy technology (such as powder sintering, compaction in the presence of a foaming agent and fiber metallurgy technology).

[0022] B. Porous Carbon Scaffold Materials

[0023] Methods for preparing porous carbon materials from polymer precursors are known in the art. For example, methods for preparing carbon materials are described in U.S. Patents Nos. 7,723,262, 8,293,818, 8,404,384, 8,654,507, 8,916,296, 9,269,502, 10,590,277, and U.S. Patent Application No. 16 / 745,197, the entire disclosures of which are incorporated herein by reference in their entirety for all purposes.

[0024] Therefore, in one embodiment, the present disclosure provides a method for preparing any of the above-mentioned carbon materials or polymer gels. The carbon material can be synthesized by the pyrolysis of a single precursor, such as a carbohydrate material, such as sucrose, fructose, glucose, dextrin, maltodextrin, starch, amylopectin, cellulose, amylose, lignin, gum arabic, and other carbohydrates and combinations thereof known in the art. Alternatively, the carbon material can be synthesized by the pyrolysis of a composite resin, for example, using a sol-gel method, i.e., using a polymer precursor (such as phenol, resorcinol, bisphenol A, urea, melamine, and other suitable compounds known in the art and combinations thereof) in a suitable solvent (such as water, ethanol, methanol, and other solvents known in the art and combinations thereof) with a crosslinking agent (such as formaldehyde, hexamethylenetetramine, furfural, and other crosslinking agents known in the art and combinations thereof). The resin can be acidic or alkaline and can contain a catalyst. The catalyst can be volatile or non-volatile. The pyrolysis temperature and dwell time (dwell) can be varied as known in the art.

[0025] In some embodiments, the method comprises preparing the polymer gel by a sol-gel process, a condensation process, or a cross-linking process involving (one or more) monomer precursors and a cross-linking agent, two existing polymers and a cross-linking agent, or a single polymer and a cross-linking agent, followed by pyrolysis of the polymer gel. The polymer gel can be dried (e.g., freeze-dried) prior to pyrolysis; however, drying is not required.

[0026] The target carbon properties can be derived from a variety of polymer chemistries, as long as the polymerization reaction produces a resin / polymer with the desired carbon backbone. Different polymer families include novolacs, resols, acrylates, styrenes, urethanes, rubbers (chloroprene, styrene-butadiene, etc.), nylons, etc. The preparation of any of these polymer resins can be carried out by many different processes, including sol-gel, emulsion / suspension, solid state, solution state, melt state, etc. for polymerization and crosslinking processes.

[0027] In some embodiments, the reactant includes phosphorus. In certain other embodiments, phosphorus is in the form of phosphoric acid. In certain other embodiments, phosphorus can be in the form of a salt, wherein the anion of the salt includes one or more phosphates, phosphites, phosphides, hydrogen phosphates, dihydrogen phosphates, hexafluorophosphates, hypophosphites, polyphosphates or pyrophosphate ions or combinations thereof. In certain other embodiments, phosphorus can be in the form of a salt, wherein the cation of the salt includes one or more phosphonium (phosphonium) ions. For those embodiments known and described in the art, any phosphate-free anion or cation pair can be selected for use in the above-mentioned embodiments. In the context, exemplary cations paired with phosphate-containing anions include but are not limited to ammonium, tetraethylammonium and tetramethylammonium ions. In the context, exemplary anions paired with phosphate-containing cations include but are not limited to carbonate ions, bicarbonate ions and acetate ions.

[0028] In some embodiments, the reactant includes sulfur. In certain other embodiments, the sulfur is in the form of sulfuric acid. In certain other embodiments, the sulfur can be in the form of a salt, wherein the anion of the salt includes one or more sulfates, sulfites, disulfides, bisulfites, hypothiocyanates, sulfons, S-methylmethionine, thiocarbonates, thiocyanates, thiophosphates, thiosilicates, or trimethylsulfonium or a combination thereof.

[0029] In some embodiments, the catalyst comprises a basic volatile catalyst. For example, in one embodiment, the basic volatile catalyst comprises ammonium carbonate, ammonium bicarbonate, ammonium acetate, ammonium hydroxide, or a combination thereof. In another embodiment, the basic volatile catalyst is ammonium carbonate. In another further embodiment, the basic volatile catalyst is ammonium acetate.

[0030] In other embodiments, the method comprises mixing acids. In certain embodiments, the acid is solid at room temperature and pressure. In some embodiments, the acid is liquid at room temperature and pressure. In some embodiments, the acid is liquid at room temperature and pressure and does not provide dissolution of one or more other polymer precursors.

[0031] In certain embodiments, the polymer precursor components are blended together and then maintained for a period of time at a temperature sufficient to achieve polymerization. The particle size of one or more of the polymer precursor components can be less than about 20 mm, such as less than 10 mm, such as less than 7 mm, such as less than 5 mm, such as less than 2 mm, such as less than 1 mm, such as less than 100 microns, such as less than 10 microns. In some embodiments, the particle size of one or more of the polymer precursor components is reduced during the blending process.

[0032] The blending of one or more polymer precursor components in the absence of a solvent can be achieved by methods described in the art, such as ball milling, jet milling, Fritsch milling, planetary mixing, and other mixing methods for mixing or blending solid particles while controlling process conditions (e.g., temperature). The mixing or blending process can be completed before, during, and / or after (or a combination thereof) incubation at the reaction temperature.

[0033] Reaction parameters include aging the blended mixture at a temperature and time sufficient to react one or more polymer precursors with each other and form a polymer. In this regard, a suitable aging temperature range is from about room temperature to a temperature at or near the melting point of one or more polymer precursors. In some embodiments, a suitable aging temperature range is from about room temperature to a temperature at or near the glass transition temperature of one or more polymer precursors. For example, in some embodiments, the solvent-free mixture is aged at a temperature of about 20°C to about 600°C, such as about 20°C to about 500°C, such as about 20°C to about 400°C, such as about 20°C to about 300°C, such as about 20°C to about 200°C. In certain embodiments, the solvent-free mixture is aged at a temperature of about 50°C to about 250°C.

[0034] The reaction duration is usually sufficient to allow the polymer precursor to react and form a polymer, for example, the mixture can be aged in 1 hour to 48 hours or longer or shorter time, depending on the desired result. Typical embodiments include aging for a period of about 2 hours to about 48 hours, for example, aging includes about 12 hours in some embodiments, and aging includes about 4 hours to 8 hours (e.g., about 6 hours) in other embodiments.

[0035] In certain embodiments, the electrochemical modifier is introduced during the above polymerization process. For example, in some embodiments, the electrochemical modifier in the form of metal particles, metal paste, metal salt, metal oxide or molten metal can be dissolved or suspended in the mixture to produce the gel resin.

[0036] Exemplary electrochemical modifiers for producing composite materials can fall into one or more than one chemical classification. In some embodiments, the electrochemical modifier is a lithium salt, such as, but not limited to, lithium fluoride, lithium chloride, lithium carbonate, lithium hydroxide, lithium benzoate, lithium bromide, lithium formate, lithium peroxide, lithium hexafluorophosphate, lithium iodate, lithium iodide, lithium perchlorate, lithium phosphate, lithium sulfate, lithium tetraborate, lithium tetrafluoroborate, and combinations thereof.

[0037] In certain embodiments, the electrochemical modifier comprises a metal, and exemplary materials include, but are not limited to, aluminum isopropoxide, manganese acetate, nickel acetate, ferric acetate, tin chloride, silicon chloride, and combinations thereof. In certain embodiments, the electrochemical modifier is a phosphate compound, including, but not limited to, phytic acid, phosphoric acid, ammonium dihydrogen phosphate, and combinations thereof. In certain embodiments, the electrochemical modifier comprises silicon, and exemplary materials include, but are not limited to, silicon powder, silicon nanotubes, polycrystalline silicon, nanocrystalline silicon, amorphous silicon, porous silicon, nanosized silicon, nanofeatured silicon, nanosized and nanofeatured silicon, silicene, and black silicon, and combinations thereof.

[0038] Electrochemical modifiers can be combined with various polymer systems by physical mixing or chemical reactions with potential (or secondary) polymer functionality. Examples of potential polymer functionality include, but are not limited to, epoxy, unsaturated (double and triple bonds), acid groups, alcohol groups, amine groups, and basic groups. Crosslinking with potential functionality can occur via heteroatoms (e.g., sulfurization with sulfur, acid / base / ring-opening reaction with phosphoric acid), reaction with organic acids or bases (as described above), coordination with transition metals (including but not limited to Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ag, Au), ring-opening or ring-closing reactions (rotaxane, spiro compounds, etc.).

[0039] Electrochemical modifiers can also be added to polymer systems by physical blending. Physical blending can include, but is not limited to, melt blending of polymers and / or copolymers, including discrete particles, chemical vapor deposition of electrochemical modifiers, and co-precipitation of electrochemical modifiers and primary polymer materials.

[0040] In some cases, the electrochemical modifier can be added via a metal salt solid, solution or suspension. The metal salt solid, solution or suspension may contain acid and / or alcohol to improve the solubility of the metal salt. In another variation, the polymer gel (before or after an optional drying step) is contacted with a paste containing an electrochemical modifier. In another variation, the polymer gel (before or after an optional drying step) is contacted with a metal or metal oxide sol containing a desired electrochemical modifier.

[0041] In addition to the electrochemical modifiers exemplified above, the composite material may include one or more other forms (i.e., allotropes) of carbon. In this regard, it has been found that the inclusion of different allotropes of carbon (e.g., graphite, amorphous carbon, conductive carbon, carbon black, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene and / or carbon fiber) into the composite material effectively optimizes the electrochemical properties of the composite material. Various allotropes of carbon can be incorporated into the carbon material at any stage of the preparation method described herein. For example, during the solution stage, during the gelation stage, during the curing stage, during the pyrolysis stage, during the grinding stage, or after grinding. In some embodiments, as described in more detail herein, by adding a second carbon form before or during the polymerization of the polymer gel, the second carbon form is incorporated into the composite material. The polymer gel containing the polymerization of the second carbon form is then processed according to the general techniques described herein to obtain a carbon material containing a second allotrope of carbon.

[0042] In other embodiments, the polymer precursor in the low or substantially solvent-free reaction mixture is a compound containing urea or amine. For example, in some embodiments, the polymer precursor is urea, melamine, hexamethylenetetramine (HMT) or a combination thereof. Other embodiments include polymer precursors selected from isocyanates or other activated carbonyl compounds (such as acid halides, etc.).

[0043] Some embodiments of the disclosed method include preparing a low or solvent-free polymer gel (and carbon material) comprising an electrochemical modifier. Such electrochemical modifiers include, but are not limited to, nitrogen, silicon, and sulfur. In other embodiments, the electrochemical modifier comprises fluorine, iron, tin, silicon, nickel, aluminum, zinc, or manganese. The electrochemical modifier may be included in the preparation procedure at any step. For example, in some cases, the electrochemical modifier is mixed with a mixture, a polymer phase, or a continuous phase.

[0044] The porous carbon material may be achieved via pyrolysis of a polymer produced from a precursor material as described above. In some embodiments, the porous carbon material comprises an amorphous activated carbon produced by pyrolysis, physical or chemical activation, or a combination thereof, in a single process step or in continuous process steps.

[0045] The temperature and residence time of pyrolysis can vary, for example, the residence time can vary from 1 min to 10 min, from 10 min to 30 min, from 30 min to 1 hour, from 1 hour to 2 hours, from 2 hours to 4 hours, from 4 hours to 24 hours. The temperature can vary, for example, the pyrolysis temperature can vary from 200 ° C to 300 ° C, from 250 ° C to 350 ° C, from 350 ° C to 450 ° C, from 450 ° C to 550 ° C, from 540 ° C to 650 ° C, from 650 ° C to 750 ° C, from 750 ° C to 850 ° C, from 850 ° C to 950 ° C, from 950 ° C to 1050 ° C, from 1050 ° C to 1150 ° C, from 1150 ° C to 1250 ° C. In some embodiments, the pyrolysis temperature varies from 650 ° C to 1100 ° C. Pyrolysis can be completed in an inert gas (e.g., nitrogen or argon).

[0046] In some embodiments, alternative gases are used to further realize carbon activation. In certain embodiments, pyrolysis and activation are combined. Suitable gases for realizing carbon activation include but are not limited to carbon dioxide, carbon monoxide, water (steam), air, oxygen and further combinations thereof. The temperature and residence time of activation can vary, for example, the residence time can vary from 1min to 10min, from 10min to 30min, from 30min to 1 hour, from 1 hour to 2 hours, from 2 hours to 4 hours, from 4 hours to 24 hours. The temperature can vary, for example, the pyrolysis temperature can vary from 200°C to 300°C, from 250°C to 350°C, from 350°C to 450°C, from 450°C to 550°C, from 540°C to 650°C, from 650°C to 750°C, from 750°C to 850°C, from 850°C to 950°C, from 950°C to 1050°C, from 1050°C to 1150°C, from 1150°C to 1250°C. In some embodiments, the temperature for combined pyrolysis and activation varies from 650°C to 1100°C.

[0047] In some embodiments, a combined pyrolysis and activation is performed to prepare the porous carbon scaffold. In such embodiments, the process gas can remain the same during the process, or the composition of the process gas can be changed during the process. In some embodiments, after sufficient temperature and time, an addition of an activation gas such as CO2, steam, or a combination thereof is added to the process gas to allow pyrolysis of the solid carbon precursor.

[0048] Suitable gases for achieving carbon activation include, but are not limited to, carbon dioxide, carbon monoxide, water (steam), air, oxygen, and further combinations thereof. The temperature and residence time of activation can vary, for example, the residence time can vary from 1 min to 10 min, from 10 min to 30 min, from 30 min to 1 hour, from 1 hour to 2 hours, from 2 hours to 4 hours, from 4 hours to 24 hours. The temperature can vary, for example, the pyrolysis temperature can vary from 200 ° C to 300 ° C, from 250 ° C to 350 ° C, from 350 ° C to 450 ° C, from 450 ° C to 550 ° C, from 540 ° C to 650 ° C, from 650 ° C to 750 ° C, from 750 ° C to 850 ° C, from 850 ° C to 950 ° C, from 950 ° C to 1050 ° C, from 1050 ° C to 1150 ° C, from 1150 ° C to 1250 ° C. In some embodiments, the activation temperature varies from 650 ° C to 1100 ° C.

[0049] Before pyrolysis, and / or after pyrolysis, and / or after activation, the carbon can be subjected to particle size reduction. The reduction of particle size can be achieved by various techniques known in the art, such as by jet milling in the presence of various gases, including air, nitrogen, argon, helium, supercritical steam, and other gases known in the art. Other particle size reduction methods are also conceivable, such as grinding, ball milling, jet milling, water jet milling, and other methods known in the art. The resulting multiple porous carbon particles are synonymously referred to as porous carbon scaffolds and porous carbon skeletons in this article.

[0050] The porous carbon support can be in the form of particles. Particle size and particle size distribution can be measured by various techniques known in the art, and can be described based on fractional volume. In this regard, the Dv50 of the carbon support can be 10nm to 10mm, for example, 100nm to 1mm, for example, 1μm to 100μm, for example, 2μm to 50μm, for example, 3μm to 30μm, for example, 4μm to 20μm, for example, 5μm to 10μm. In certain embodiments, Dv50 is less than 1mm, for example, less than 100μm, for example, less than 50μm, for example, less than 30μm, for example, less than 20μm, for example, less than 10μm, for example, less than 8μm, for example, less than 5μm, for example, less than 3μm, for example, less than 1μm. In certain embodiments, Dv100 is less than 1 mm, for example, less than 100 μm, for example, less than 50 μm, for example, less than 30 μm, for example, less than 20 μm, for example, less than 10 μm, for example, less than 8 μm, for example, less than 5 μm, for example, less than 3 μm, for example, less than 1 μm. In certain embodiments, Dv99 is less than 1 mm, for example, less than 100 μm, for example, less than 50 μm, for example, less than 30 μm, for example, less than 20 μm, for example, less than 10 μm, for example, less than 8 μm, for example, less than 5 μm, for example, less than 3 μm, for example, less than 1 μm. In certain embodiments, Dv90 is less than 1 mm, for example, less than 100 μm, for example, less than 50 μm, for example, less than 30 μm, for example, less than 20 μm, for example, less than 10 μm, for example, less than 8 μm, for example, less than 5 μm, for example, less than 3 μm, for example, less than 1 μm. In certain embodiments, Dv0 is greater than 10 nm, such as greater than 100 nm, such as greater than 500 nm, such as greater than 1 μm, such as greater than 2 μm, such as greater than 5 μm, such as greater than 10 μm. In certain embodiments, Dv1 is greater than 10 nm, such as greater than 100 nm, such as greater than 500 nm, such as greater than 1 μm, such as greater than 2 μm, such as greater than 5 μm, such as greater than 10 μm. In certain embodiments, Dv10 is greater than 10 nm, such as greater than 100 nm, such as greater than 500 nm, such as greater than 1 μm, such as greater than 2 μm, such as greater than 5 μm, such as greater than 10 μm.

[0051] In some embodiments, the surface area of ​​the porous carbon support may include greater than 400 m 2 / g, for example, greater than 500m 2 / g, for example, greater than 750m 2 / g, for example, greater than 1000m 2 / g, for example, greater than 1250m 2 / g, for example, greater than 1500m 2 / g, for example, greater than 1750m 2 / g, for example, greater than 2000m 2 / g, for example, greater than 2500m 2 / g, for example, greater than 3000m 2 In other embodiments, the surface area of ​​the porous carbon support may be less than 500 m 2 In some embodiments, the surface area of ​​the porous carbon support is 200 m 2 / g to 500m 2 In some embodiments, the surface area of ​​the porous carbon support is 100 m 2 / g to 200m 2 / g. In some embodiments, the surface area of ​​the porous carbon support is 50m 2 / g to 100m 2 / g. In some embodiments, the surface area of ​​the porous carbon support is 10m 2 / g to 50m 2 In some embodiments, the surface area of ​​the porous carbon support can be less than 10 m 2 / g.

[0052] In some embodiments, the pore volume of the porous carbon scaffold is greater than 0.4 cm 3 / g, for example, greater than 0.5cm 3 / g, for example, greater than 0.6cm 3 / g, for example, greater than 0.7cm 3 / g, for example, greater than 0.8cm 3 / g, for example, greater than 0.9cm 3 / g, for example, greater than 1.0 cm 3 / g, for example, greater than 1.1cm 3 / g, for example, greater than 1.2cm 3 / g, for example, greater than 1.4cm 3 / g, for example, greater than 1.6cm 3 / g, for example, greater than 1.8cm 3 / g, for example, greater than 2.0cm 3 In other embodiments, the pore volume of the porous carbon scaffold is less than 0.5 cm 3 / g, for example 0.1cm 3 / g to 0.5cm 3 In certain other embodiments, the pore volume of the porous carbon scaffold is 0.01 cm 3 / g to 0.1cm 3 / g.

[0053] In some other embodiments, the porous carbon scaffold has a 0.2 cm 3 / g to 2.0cm 3 / g pore volume of amorphous activated carbon. In certain embodiments, the carbon is 0.4cm 3 / g to 1.5cm 3 / g of pore volume. In certain embodiments, the carbon is an amorphous activated carbon having a pore volume of 0.5 cm 3 / g to 1.2cm 3 / g pore volume of amorphous activated carbon. In certain embodiments, the carbon is 0.6 cm 3 / g to 1.0cm 3 / g of amorphous activated carbon.

[0054] In some other embodiments, the porous carbon scaffold comprises less than 1.0 g / cm 3 , for example, less than 0.8 g / cm 3 , for example, less than 0.6 g / cm 3 , for example, less than 0.5 g / cm 3 , for example, less than 0.4 g / cm 3 , for example, less than 0.3 g / cm 3 , for example, less than 0.2 g / cm 3 , for example, less than 0.1 g / cm 3 The tap density.

[0055] The surface functionality of the porous carbon scaffold can vary. One property that can predict the surface functionality is the pH of the porous carbon scaffold. The porous carbon scaffolds of the present disclosure include pH values ​​of less than 1 to about 14, such as less than 5, 5 to 8, or greater than 8. In some embodiments, the pH of the porous carbon is less than 4, less than 3, less than 2, or even less than 1. In other embodiments, the pH of the porous carbon is about 5 to 6, about 6 to 7, about 7 to 8, or 8 to 9, or 9 to 10. In other embodiments, the pH is high and the pH range of the porous carbon is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.

[0056] The pore volume distribution of the porous carbon scaffold can vary. For example, the % micropores can include less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, such as less than 0.1%. In certain embodiments, there is no detectable micropore volume in the porous carbon scaffold.

[0057] The mesopores comprising the porous carbon scaffold can vary. For example, the % mesopores can include less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, such as less than 0.1%. In certain embodiments, there is no detectable mesopore volume in the porous carbon scaffold.

[0058] In some embodiments, the pore volume distribution of the porous carbon scaffold includes greater than 50% macropores, such as greater than 60% macropores, such as greater than 70% macropores, such as greater than 80% macropores, such as greater than 90% macropores, such as greater than 95% macropores, such as greater than 98% macropores, such as greater than 99% macropores, such as greater than 99.5% macropores, such as greater than 99.9% macropores.

[0059] In certain preferred embodiments, the pore volume of the porous carbon scaffold includes a mixture of micropores, mesopores and macropores. Thus, in certain embodiments, the porous carbon scaffold includes 0 to 20% micropores, 30% to 70% mesopores and less than 10% macropores. In certain other embodiments, the porous carbon scaffold includes 0 to 20% micropores, 0 to 20% mesopores and 70% to 95% macropores. In certain other embodiments, the porous carbon scaffold includes 20% to 50% micropores, 50% to 80% mesopores and 0 to 10% macropores. In certain other embodiments, the porous carbon scaffold includes 40% to 60% micropores, 40% to 60% mesopores and 0 to 10% macropores. In certain other embodiments, the porous carbon scaffold includes 80% to 95% micropores, 0 to 10% mesopores and 0 to 10% macropores. In certain other embodiments, the porous carbon scaffold includes 0 to 10% micropores, 30% to 50% mesopores and 50% to 70% macropores. In certain other embodiments, the porous carbon scaffold comprises 0 to 10% micropores, 70% to 80% mesopores, and 0 to 20% macropores. In certain other embodiments, the porous carbon scaffold comprises 0 to 20% micropores, 70% to 95% mesopores, and 0 to 10% macropores. In certain other embodiments, the porous carbon scaffold comprises 0 to 10% micropores, 70% to 95% mesopores, and 0 to 20% macropores.

[0060] In certain embodiments, the percentage of pore volume in the porous carbon scaffold representing pores of 100A to 1000A (10nm to 100nm) includes greater than 30% of the total pore volume, such as greater than 40% of the total pore volume, such as greater than 50% of the total pore volume, such as greater than 60% of the total pore volume, such as greater than 70% of the total pore volume, such as greater than 80% of the total pore volume, such as greater than 90% of the total pore volume, such as greater than 95% of the total pore volume, such as greater than 98% of the total pore volume, such as greater than 99% of the total pore volume, such as greater than 99.5% of the total pore volume, such as greater than 99.9% of the total pore volume.

[0061] In certain embodiments, the porous carbon scaffold has a pycnometry density of about 1 g / cc to about 3 g / cc, such as about 1.5 g / cc to about 2.3 g / cc. In other embodiments, the skeletal density ranges from about 1.5 cc / g to about 1.6 cc / g, about 1.6 cc / g to about 1.7 cc / g, about 1.7 cc / g to about 1.8 cc / g, about 1.8 cc / g to about 1.9 cc / g, about 1.9 cc / g to about 2.0 cc / g, about 2.0 cc / g to about 2.1 cc / g, about 2.1 cc / g to about 2.2 cc / g, or about 2.2 cc / g to about 2.3 cc / g, about 2.3 cc / g to about 2.4 cc / g, such as about 2.4 cc / g to about 2.5 cc / g.

[0062] In some embodiments, the carbon support pore volume distribution can be described as the number or volume distribution of pores determined based on gas adsorption analysis (e.g., nitrogen adsorption analysis) as known in the art. In some embodiments, the pore size distribution can be expressed in terms of the pore size at which a certain portion of the total pore volume is at or less than. For example, the pore size at which 10% of the pores are present or less can be expressed as DPv10.

[0063] The DPv10 for the porous carbon scaffold can vary, for example, the DPv10 can be less than 100 nm, for example, 0.1 nm to 100 nm, for example, 1 nm to 100 nm, for example, 1 nm to 50 nm, for example, 1 nm to 40 nm, for example, 1 nm to 30 nm, for example, 1 nm to 10 nm, for example, 1 nm to 5 nm. In certain embodiments, the DPv10 can be less than 100 nm, for example, less than 50 nm, for example, less than 10 nm, for example, less than 5 nm, for example, less than 4 nm, for example, less than 3 nm, for example, less than 2 nm, for example, less than 1 nm. The DPv10 of the porous carbon scaffold can vary, for example, the DPv10 can be less than 100 nm, for example, 0.1 nm to 100 nm, for example, 1 nm to 100 nm, for example, 1 nm to 50 nm, for example, 1 nm to 40 nm, for example, 1 nm to 30 nm, for example, 1 nm to 10 nm, for example, 1 nm to 5 nm. In certain embodiments, DPv10 can be less than 100 nm, such as less than 50 nm, such as less than 10 nm, such as less than 5 nm, such as less than 4 nm, such as less than 3 nm, such as less than 2 nm, such as less than 1 nm.

[0064] In certain embodiments, DPv20 may vary, for example, may be less than 100 nm, for example, less than 50 nm, for example, less than 10 nm, for example, less than 9 nm, for example, less than 8 nm, for example, less than 7 nm, for example, less than 6 nm, for example, less than 5 nm, for example, less than 4 nm, for example, less than 3 nm, for example, less than 2 nm, for example, less than 1 nm.

[0065] The DPv50 of the porous carbon scaffold can vary, for example, the DPv50 can be 0.01 nm to 100 nm, for example, 0.1 nm to 100 nm, for example, 1 nm to 100 nm, for example, 1 nm to 50 nm, for example, 1 nm to 40 nm, for example, 1 nm to 30 nm, for example, 1 nm to 10 nm, for example, 1 nm to 5 nm. In other embodiments, the DPv50 is 2 nm to 100 nm, for example, 2 nm to 50 nm, for example, 2 nm to 30 nm, for example, 2 nm to 20 nm, for example, 2 nm to 15 nm, for example, 2 nm to 10 nm, for example, 6 nm to 18 nm, for example, 8 nm to 16 nm, for example, 8 nm to 14 nm, for example, 8 nm to 12 nm.

[0066] The DPv80 for the porous carbon scaffold can vary, for example, the DPv80 can be 0.01 nm to 100 nm, for example, 0.1 nm to 100 nm, for example, 1 nm to 100 nm, for example, 1 nm to 50 nm, for example, 1 nm to 50 nm, for example, 1 nm to 40 nm, for example, 1 nm to 30 nm, for example, 1 nm to 10 nm, for example, 1 nm to 5 nm. In other embodiments, the DPv80 is 5 nm to 30 nm, for example, 10 nm to 30 nm, for example, 10 nm to 20 nm, for example, 12 nm to 18 nm, for example, 12 nm to 16 nm, for example, 14 nm to 18 nm.

[0067] In some embodiments, DPv80 is less than 100nm, such as less than 50nm, such as less than 40nm, such as less than 30nm, such as less than 20nm, such as less than 15nm, such as less than 10nm, such as DPv90 is less than 5nm, such as DPv90 is less than 4nm, such as DPv90 is less than 3nm. In some embodiments, the carbon support includes a pore volume having greater than 70% micropores and DPv80 less than 100nm (e.g., DPv80 is less than 50nm, such as DPv80 is less than 40nm, such as DPv80 is less than 30nm, such as DPv80 is less than 20nm, such as DPv80 is less than 15nm, such as DPv80 is less than 10nm, such as DPv80 is less than 5nm, such as DPv80 is less than 4nm, such as DPv80 is less than 3nm). In other embodiments, the carbon scaffold comprises a pore volume having greater than 80% micropores and a DPv80 less than 100 nm (e.g., DPv80 less than 50 nm, e.g., DPv80 less than 40 nm, e.g., DPv80 less than 30 nm, e.g., DPv80 less than 20 nm, e.g., DPv80 less than 15 nm, e.g., DPv80 less than 10 nm, e.g., DPv80 less than 5 nm, e.g., DPv80 less than 4 nm, e.g., DPv80 less than 3 nm).

[0068] The DPv90 of the porous carbon scaffold can vary, for example, the DPv90 can be 0.01 nm to 100 nm, for example, 0.1 nm to 100 nm, for example, 1 nm to 100 nm, for example, 1 nm to 50 nm, for example, 1 nm to 50 nm, for example, 1 nm to 40 nm, for example, 1 nm to 30 nm, for example, 1 nm to 10 nm, for example, 1 nm to 5 nm. In other embodiments, the DPv50 is 2 nm to 100 nm, for example, 2 nm to 50 nm, for example, 2 nm to 30 nm, for example, 2 nm to 20 nm, for example, 2 nm to 15 nm, for example, 2 nm to 10 nm. In other embodiments, the DPv90 is 5 nm to 30 nm, for example, 10 nm to 30 nm, for example, 15 nm to 25 nm, for example, 16 nm to 24 nm, for example, 18 nm to 24 nm, for example, 8 nm to 10 nm.

[0069] In some embodiments, the DPv90 is less than 100 nm, such as less than 50 nm, such as less than 40 nm, such as less than 30 nm, such as less than 20 nm, such as less than 15 nm, such as less than 10 nm. In some embodiments, the carbon scaffold comprises a pore volume having greater than 70% micropores and a DPv90 of less than 100 nm (e.g., DPv90 of less than 50 nm, such as DPv90 of less than 40 nm, such as DPv90 of less than 30 nm, such as DPv90 of less than 20 nm, such as DPv90 of less than 15 nm, such as DPv90 of less than 10 nm, such as DPv90 of less than 5 nm, such as DPv90 of less than 4 nm, such as DPv90 of less than 3 nm). In other embodiments, the carbon support comprises a pore volume having greater than 80% micropores and a DPv90 less than 100 nm (e.g., DPv90 less than 50 nm, e.g., DPv90 less than 40 nm, e.g., DPv90 less than 30 nm, e.g., DPv90 less than 20 nm, e.g., DPv90 less than 15 nm, e.g., DPv90 less than 10 nm, e.g., DPv90 less than 5 nm, e.g., DPv90 less than 4 nm, e.g., DPv90 less than 3 nm).

[0070] The DPv99 of the porous carbon scaffold can vary, for example, the DPv99 can be 0.01 nm to 1000 nm, for example, 0.1 nm to 1000 nm, for example, 1 nm to 500 nm, for example, 1 nm to 200 nm, for example, 1 nm to 150 nm, for example, 1 nm to 100 nm, for example, 1 nm to 50 nm, for example, 1 nm to 20 nm. In other embodiments, the DPv99 is 2 nm to 500 nm, for example, 2 nm to 200 nm, for example, 2 nm to 150 nm, for example, 2 nm to 100 nm, for example, 2 nm to 50 nm, for example, 2 nm to 20 nm, for example, 2 nm to 15 nm, for example, 2 nm to 10 nm. In certain embodiments, the porous carbon scaffold comprises a pore volume having greater than 70% micropores and a DPv99 of less than 50 nm, such as less than 40 nm, such as less than 30 nm, such as less than 20 nm, such as less than 10 nm, such as less than 8 nm, such as less than 6 nm, such as less than 5 nm, such as less than 4 nm, such as less than 3 nm. In certain embodiments, the porous carbon scaffold comprises a pore volume having greater than 80% micropores and a DPv99 of less than 50 nm, such as less than 40 nm, such as less than 30 nm, such as less than 20 nm, such as less than 10 nm, such as less than 8 nm, such as less than 6 nm, such as less than 5 nm, such as less than 4 nm, such as less than 3 nm.

[0071] In some embodiments, the carbon support is modified prior to lithium impregnation. For example, in some embodiments, the surface of the carbon pores is functionalized to produce a more lithiophilic surface, i.e., a surface that preferentially interacts with lithium or lithium-containing precursor materials, wherein the preferential interaction can be manifested as preferential diffusion, deposition, adsorption, etc.

[0072] C. Lithium impregnation in porous carbon or silicon-carbon composites via chemical vapor infiltration (CVI)

[0073] Chemical vapor deposition (CVD) is a process in which a substrate provides a solid surface including a first component of a composite, and a gas is thermally decomposed on the solid surface to provide a second component of the composite. This CVD method can be used, for example, to produce a Li-C composite material, in which lithium is coated on the outer surface of carbon particles. Alternatively, chemical vapor infiltration (CVI) is a process in which a substrate provides a porous support or is described as a porous skeleton, and a gas is thermally decomposed in the pores of the porous support to provide a second component of the composite material. In a preferred embodiment, the porous support is a porous carbon support, and the gas is a silane gas that is thermally decomposed into silicon to provide a silicon-carbon composite material. The CVI reactor can be batch or continuous. The CVI reactor type can vary, for example, it can be a static bed reactor, a moving bed reactor, a rotary kiln, a vibration heat-assisted reactor according to US2021 / 045417, a fluidized bed reactor, or other types of reactors known in the art. According to one embodiment of the present invention, the third component is also in the pores of the porous carbon support, or exists as a separate phase or is alloyed in the silicon phase, wherein the third component is impregnated into the material via CVI. According to this embodiment, a lithium-silicon alloy-carbon composite is produced by a method comprising the following steps:

[0074] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0075] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0076] c. heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon-carbon composite.

[0077] In certain embodiments, heating the silicon-carbon composite material in the presence of a lithium-containing precursor causes alloying of lithium and silicon to provide a lithium-silicon alloy phase. According to this embodiment, the lithium-silicon alloy-carbon composite is produced by a method comprising the steps of:

[0078] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0079] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0080] c. heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon alloy-carbon composite.

[0081] In some embodiments, the silicon-carbon composite is heated in the presence of a lithium-containing precursor to cause the production of a lithium-silicon-carbon composite, wherein the lithium includes both lithium-silicon alloy domains and non-alloy domains. According to this embodiment, the lithium-silicon alloy-carbon composite is produced by a method comprising the steps of:

[0082] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0083] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0084] c. Heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon alloy silicon-carbon composite, wherein the lithium also includes non-silicon-alloy domains.

[0085] In some embodiments, a porous carbon scaffold is used to perform lithium CVI to introduce lithium into the pores of the porous carbon, followed by silicon CVI to produce silicon and / or lithium-silicon alloys or combinations thereof within the carbon porosity. According to this embodiment, a lithium-silicon alloy-carbon composite is produced by a method comprising the following steps:

[0086] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0087] b. Heating the carbon framework in the presence of a lithium-containing precursor to produce a lithium-carbon composite

[0088] c. Heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite material.

[0089] In a related embodiment, the lithium is present within the carbon pores in the form of lithium alloyed with silicon.

[0090] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0091] b. Heating the carbon framework in the presence of a lithium-containing precursor to produce a lithium-carbon composite

[0092] c. Heating the lithium-carbon composite at elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon alloy-carbon composite. In a related embodiment, the lithium is present in the carbon pores in the form of lithium and an alloy with silicon.

[0093] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0094] b. Heating the carbon framework in the presence of a lithium-containing precursor to produce a lithium-carbon composite

[0095] c. heating the silicon-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon alloy-carbon composite material,

[0096] The lithium also includes non-silicon-alloy domains.

[0097] In certain embodiments, the lithium-containing precursor is introduced in the form of a gas. In certain other embodiments, the lithium-containing precursor is introduced in solid or liquid form and converted to a gaseous form under the conditions of the alloying process. The gasified lithium-containing precursor can be mixed with other inert gases (e.g., nitrogen, argon, and combinations thereof). The temperature and time of the treatment for introducing lithium into the silicon-carbon composite can be varied, for example, the temperature can be between 100°C and 1700°C, for example, between 100°C and 300°C, for example, between 300°C and 400°C, for example, between 400°C and 500°C, for example, between 500°C and 600°C, for example, between 600°C and 700°C, for example, between 700°C and 800°C, for example, between 800°C and 900°C, for example, between 900°C and 1000°C, for example, between 1000°C and 1100°C, for example, between 1100°C and 1200°C, for example, between 1200°C and 1400°C, for example, between 1300°C and 1400°C, for example, between 1400°C and 1700°C.

[0098] In one embodiment, the lithium is heated to achieve gasification at or above its boiling point (1330°C). In other embodiments, the lithium-containing precursor is heated to or above its boiling point to achieve gasification. In this regard, exemplary lithium-containing precursors include, but are not limited to, lithium bis(trimethylsilyl)amide (boiling point = 84°C), lithium acetylsalicylate (boiling point = 350°C), lithium amide (boiling point = 430°C), lithium bromide (boiling point = 1265°C), lithium borohydride (boiling point = 380°C), lithium chloride (boiling point = 1383°C), lithium hydride (boiling point = 950°C), and lithium hydroxide (boiling point = 1626°C).

[0099] The pressure of the lithium CVI process can vary. In some embodiments, the pressure is atmospheric pressure. In some embodiments, the pressure is below atmospheric pressure. In some embodiments, the pressure is above atmospheric pressure.

[0100] In some embodiments, the silicon CVI process is followed by a lithium CVI process. In other embodiments, silicon and lithium are simultaneously introduced by a co-CVI process. Without being bound by theory, the presence of hydrogen as a decomposition product of silane decomposition provides a reducing environment to promote lithium reduction and / or lithium and silicon alloying in carbon pores. According to some embodiments, the conversion of lithium-containing precursors to lithium can be achieved by various methods such as chemical reduction or electrochemical reduction. In certain embodiments, reduction is achieved via a reaction with a reducing gas environment (e.g., hydrogen).

[0101] D. Lithium impregnation in porous carbon or silicon-carbon composites by intrusion

[0102] Melt intrusion is a process in which a liquid infiltrates the pores of a porous scaffold material. This melt intrusion method can be used, for example, to produce a lithium-silicon-carbon composite material produced by a method comprising the steps of:

[0103] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0104] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0105] c. Melting a lithium precursor in the presence of a silicon-carbon composite to produce a lithium-silicon-carbon composite.

[0106] In certain embodiments, melting a lithium precursor in the presence of a silicon-carbon composite material causes alloying of lithium and silicon to provide a lithium-silicon alloy phase. According to this embodiment, a lithium-silicon alloy-carbon composite is produced by a method comprising:

[0107] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0108] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0109] c. Melting a lithium precursor in the presence of a silicon-carbon composite to produce a lithium-silicon alloy-carbon composite.

[0110] In some embodiments, melting a lithium precursor in the presence of a silicon-carbon composite material results in the production of a lithium-silicon-carbon composite material, wherein the lithium includes both lithium-silicon alloy domains and non-alloy domains. According to this embodiment, the lithium-silicon alloy-carbon composite is produced by a method comprising the steps of:

[0111] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0112] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0113] c. Melting a lithium precursor in the presence of a silicon-carbon composite to produce a lithium-silicon alloy-carbon composite, wherein the lithium also includes non-silicon-alloy domains.

[0114] In some embodiments, silicon and lithium are simultaneously incorporated into the porous carbon framework according to the co-processing of silane CVI and lithium precursor melt intrusion to produce the following lithium-silicon alloy-carbon composite:

[0115] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0116] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas and a lithium precursor, wherein the elevated temperature is above the melting point of the lithium precursor to impregnate silicon and lithium into one or more pores of the porous carbon framework; and

[0117] c. Wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

[0118] In some embodiments, lithium intrusion is accomplished prior to silicon CVI to produce a lithium-silicon alloy-carbon composite as follows:

[0119] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0120] b. melting a lithium precursor in the presence of the carbon skeleton material to produce a lithium-silicon composite material;

[0121] c. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite material; and

[0122] d. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

[0123] The pressure used for the melt intrusion process can vary. In some embodiments, the pressure is atmospheric pressure. In some embodiments, the pressure is below atmospheric pressure. In some embodiments, the pressure is above atmospheric pressure.

[0124] The temperature at which melt intrusion is completed may vary, for example, the temperature may be 25°C to 1000°C, for example 25°C to 100°C, for example 100°C to 200°C, for example 200°C to 300°C, for example 300°C to 400°C, for example 400°C to 500°C, for example 500°C to 600°C, for example 600°C to 700°C, for example 700°C to 800°C, for example 800°C to 900°C, for example 900°C to 1000°C.

[0125] According to the melt intrusion process, the lithium can be in the form of elemental lithium, and the temperature of the process can vary, for example at or above the melting point of lithium (180.5° C.). In other embodiments, the lithium is contained within a lithium-containing precursor that is heated at or above its melting point to facilitate the melt intrusion process. In this regard, exemplary lithium-containing precursors include, but are not limited to, lithium carbonate (melting point = 723°C), lithium acetate (melting point = 286°C), lithium amide (melting point = 374°C), lithium bromide (melting point = 550°C), lithium borohydride (melting point = 268°C), lithium chloride (melting point = 610°C), lithium fluoride (melting point = 846°C), lithium hydride (melting point = 689°C), and lithium hydroxide (melting point = 471°C), lithium hydrogen sulfate (melting point = 171°C), lithium dihydrogen phosphate (melting point = 100°C), lithium nitrate (melting point = 261°C), lithium phosphate (melting point = 837°C), lithium nitride (melting point = 813°C), lithium sulfate (melting point = 860°C), lithium sulfide (melting point = 950°C), lithium disulfide (melting point = 370°C), and lithium sulfite (melting point = 455°C). Additional exemplary lithium-containing precursors include lithium metal alloys including lithium aluminum alloy (melting point = 718°C), lithium aluminum copper alloy (melting point 600°C to 655°C), lithium tin alloy (melting point 344°C to 488°C), and lithium silicon alloy (melting point = 700°C).

[0126] In some embodiments, the non-lithium components of the lithium precursor are retained in the lithium-silicon-carbon composite material and can be optionally used as an electrochemical modifier. In other embodiments, the non-lithium components of the lithium precursor are removed, for example, by decomposition, extraction, or other methods known in the art. In some embodiments, any lithium retained outside the carbon pores or porous carbon support can be removed by solvent washing, wherein exemplary solvents include but are not limited to tetrahydrofuran, toluene, or a combination thereof. In some embodiments, the lithium precursor introduced into the porous carbon by melt intrusion is converted into lithium by chemical or electrochemical reduction methods. Alternatively, the conversion of the lithium-containing precursor to lithium can be achieved by various methods such as chemical or electrochemical reduction. In certain embodiments, reduction is achieved by reaction with a reducing gas environment (e.g., hydrogen).

[0127] Exemplary reagents for effecting the reduction of a lithium-containing precursor to lithium include, but are not limited to, hydride reagents and dihydride, lithium aluminum hydride, borohydrides such as sodium borohydride or diborane, metal and organometallic reagents such as Grignard reagents, and dialkylcopperlithium (dialkylcuprate) reagents such as sodium, sodium alkyls, and lithium alkyls.

[0128] The melt intrusion process can be carried out in batches. Alternatively, the melt intrusion process can be carried out as a continuous process. In some embodiments, the melt intrusion process can be carried out as a continuous process using extrusion.

[0129] Solution or suspension intrusion is a process in which a solution or suspension of a lithium precursor penetrates into the pores of a porous carbon framework. This solution or suspension intrusion method can be used, for example, to produce a lithium-silicon-carbon composite material produced by a method comprising the steps of:

[0130] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0131] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework to provide a silicon-carbon composite material;

[0132] c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; and

[0133] d. Reducing the lithium precursor to produce a lithium-silicon-carbon composite material.

[0134] In certain embodiments, the solution or suspension intrusion causes alloying of lithium and silicon to provide a lithium-silicon alloy phase. According to this embodiment, a lithium-silicon alloy-carbon composite is produced by a method comprising the steps of:

[0135] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0136] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0137] c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; and

[0138] d. Reducing the lithium precursor to produce a lithium-silicon alloy-carbon composite material.

[0139] In some embodiments, the solution or suspension intrusion causes the production of a lithium-silicon-carbon composite material, wherein the lithium includes both lithium-silicon alloy domains and non-alloy domains. According to this embodiment, the lithium-silicon alloy-carbon composite is produced by a method comprising the steps of:

[0140] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0141] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material;

[0142] c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; and

[0143] d. Reducing the lithium precursor to produce a lithium-silicon alloy-carbon composite material, wherein the lithium also includes non-silicon-alloy domains.

[0144] In some embodiments, solution or suspension intrusion and reduction are accomplished prior to silicon CVI to produce a lithium-silicon alloy-carbon composite as follows:

[0145] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0146] b. contacting the porous carbon framework with a solution or suspension of a lithium precursor to incorporate the lithium precursor into one or more pores of the porous carbon framework;

[0147] c. reducing a lithium precursor to produce a lithium-carbon composite;

[0148] d. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite; and

[0149] e. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

[0150] In other embodiments, solution or suspension intrusion is completed prior to silicon CVI, and reduction occurs during the silicon CIV process to produce a lithium-silicon alloy-carbon composite as follows:

[0151] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0152] b. contacting the porous carbon framework with a solution or suspension of a lithium precursor to incorporate the lithium precursor into one or more pores of the porous carbon framework;

[0153] c. heating the carbon skeleton containing a lithium precursor at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon skeleton, thereby providing a lithium-silicon-carbon composite material;

[0154] as well as

[0155] d. Wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

[0156] The environment of the solution or suspension invasion can vary. For example, the environment can be aqueous. Alternatively, the environment can be organic based. One such example for solution invasion is a solute of lithium naphthalene, lithium biphenyl, lithium methyl biphenyl or similar substances, where the methyl and / or phenyl groups are present as di-, tri-, tetra- or combinations thereof in an ether solvent (e.g., an aprotic ether solvent such as tetrahydrofuran, diethyl ether or dimethoxyethane, etc., or combinations thereof).

[0157] The solution or suspension intrusion can be performed in various process steps. In one embodiment, the porous carbon skeleton is introduced into a solution or suspension of a lithium precursor, and the particles of the porous carbon skeleton are kept suspended, such as by mixing, shaking, extruding, or other such suspension methods known in the art. In some embodiments, the porous carbon skeleton containing the lithium precursor is removed from the solution or suspension, such as by centrifugation, fluidized bed drying, vacuum drying, drying at atmospheric pressure, or other methods known in the art, or a combination thereof.

[0158] Exemplary lithium precursors for achieving solution or suspension intrusion into one or more pores of the porous carbon framework vary. In this regard, exemplary lithium precursors include, but are not limited to, lithium carbonate, lithium acetate, lithium peroxide, lithium amide, lithium bromide, lithium borohydride, lithium chloride, lithium fluoride, lithium hydride, lithium hydroxide, lithium hydrogen sulfate, lithium dihydrogen phosphate, lithium nitrate, lithium phosphate, lithium nitride, lithium sulfate, lithium sulfide, lithium disulfide, lithium sulfite, and combinations thereof.

[0159] In some embodiments, the non-lithium components of the lithium precursor are retained in the lithium-silicon-carbon composite and can be optionally used as an electrochemical modifier. In other embodiments, the non-lithium components of the lithium precursor are removed, for example, by decomposition, extraction, or other methods known in the art. In some embodiments, any lithium retained outside the carbon pores or porous carbon support can be removed by solvent washing, wherein exemplary solvents include but are not limited to naphthalene, toluene, or a combination thereof. In some embodiments, the lithium precursor introduced into the porous carbon by melt intrusion is converted into lithium by a chemical or electrochemical reduction method.

[0160] Exemplary reagents for achieving the reduction of lithium-containing precursors to lithium include, but are not limited to, hydride reagents and dihydride, lithium aluminum hydride, borohydrides such as sodium borohydride or diborane, metal and organometallic reagents such as Grignard reagents, and dialkyl copper lithium (dialkyl copper acid lithium) reagents such as sodium, alkyl sodium and alkyl lithium. Alternatively, the conversion of lithium-containing precursors to lithium can be achieved by various methods such as chemical or electrochemical reduction. In certain embodiments, reduction is achieved via reaction with a reducing gas environment (e.g., hydrogen).

[0161] The solution or suspension intrusion process can be carried out in batches. Alternatively, the solution or suspension intrusion process can be carried out as a continuous process. In some embodiments, the solution or suspension intrusion process can be carried out as a continuous process using extrusion.

[0162] E. Incorporation of lithium into silicon-carbon composites by co-processing lithium and carbon precursors

[0163] In some embodiments, the carbon and lithium precursors are co-processed to produce a lithium-silicon-carbon composite. Thus, the lithium precursor is incorporated into the carbon precursor, and the mixture is pyrolyzed and activated to produce a porous carbon scaffold containing the lithium precursor, and the scaffold is subjected to CVI in the presence of a silicon-containing gas to produce a lithium-silicon-carbon composite.

[0164] According to some embodiments, the melting of the lithium-containing precursor is no greater than the temperature for completing pyrolysis and / or activation to convert the carbon precursor into carbon. In such an embodiment, the lithium-containing precursor can be lithium metal. In other embodiments, the lithium-containing precursor can be a lithium-containing material disclosed elsewhere in the present disclosure. In some embodiments, the melting and conversion temperature of the lithium-containing precursor is no greater than the temperature for completing pyrolysis and / or activation to convert the carbon precursor into carbon. Therefore, the conversion of the lithium-containing precursor to lithium can be achieved by various methods such as chemical or electrochemical reduction. In certain embodiments, reduction is achieved via a reaction with a reducing gas environment (e.g., hydrogen).

[0165] Exemplary lithium-containing salts useful as precursors include, but are not limited to, dilithium tetrabromonickelate (II), dilithium tetrachlorocuprate (II), lithium azide, lithium nitrate, lithium nitride, lithium benzoate, lithium bromide, lithium carbonate, lithium chloride, lithium cyclohexanebutyrate, lithium fluoride, lithium formate, lithium hexafluoroarsenate (V), lithium hexafluorophosphate, lithium hydroxide, lithium iodate, lithium iodide, lithium metaborate, lithium perchlorate, lithium phosphate, lithium peroxide, lithium sulfate, lithium tetraborate, lithium tetrachloroaluminate, lithium tetrafluoroborate, lithium thiocyanate, lithium trifluoromethanesulfonate, lithium triflate, lithium acetate, lithium formate, and combinations thereof.

[0166] F. Lithium Impregnation into Silicon-Carbon Composites by Electroplating

[0167] In one embodiment, the lithium-silicon-carbon composite can be synthesized by an electroplating mechanism, wherein the electrolytic cell is assembled with a porous carbon working electrode (prepared by slurry casting on a copper foil or nickel sheet collector) and a lithium metal counter electrode (counter electrode) separated from each other in a liquid electrolyte containing a lithium salt (e.g., LiPF6, LiFSI, LiTFSI, LiCl, LiBr, LiI, LiNO3, etc.) and an anhydrous organic solvent (e.g., propylene carbonate, ethylene carbonate, 1,3-dioxolane, 1,2-dimethoxyethane, tetrahydrofuran, acetonitrile, etc.). A negative bias voltage (e.g., -1V, -2V, -3V, -4V, -5V, -6V, etc.) is applied to promote Li+ reduction in the porous carbon electrode. The amount of charge transferred (Ah) is used to track the Li metal load, and the applied voltage is then stopped once the desired Li load is achieved. The electrode containing the lithium-silicon-carbon composite can then be transferred to a Li-ion battery and used as an anode.

[0168] Therefore, the porous electrode comprising the silicon-carbon composite is prepared on a roll-to-roll coater, which is subsequently transferred to an electrolytic cell (as described above) contained in an inert atmosphere, in which a negative bias voltage is applied as described in the above embodiment, and lithium plating is performed while the electrode is continuously moving on the roller. Therefore, the degree of lithium metal loading is determined by the conveying speed of the roll-to-roll device. In addition, the electrolytic cell may include a dissolved polymer (e.g., polyacrylonitrile, polyvinylidene fluoride, polydopamine, etc.) so that when the electrode leaves the groove and is subsequently dried, the polymer film remains on the electrode surface, acting as a barrier to the atmosphere, thereby minimizing the oxidation of the lithium metal formed in the porous carbon.

[0169] In an alternative more preferred embodiment, lithium alloying can be performed in situ in an assembled Li-ion battery, wherein a porous electrode comprising a silicon-carbon composite is the anode and a conventional Li-containing transition metal oxide as known in the art (e.g., LiFePO4, LiCoO2, NCA, NMC111, NMC532, NMC622, etc.) is used as the cathode. Lithium plating occurs when the battery is charged to its 100% charged operating voltage (e.g., 4.2V). In this "anode-free" configuration, the Li+ source is the cathode. When the battery is discharged, the process is reversed (Li+ is stripped from the porous carbon electrode). This embodiment is preferred because it does not require handling of active lithium metal in an environment external to the battery, and because the cathode serves as the only source of Li+ in the system, the energy density of the battery can be improved.

[0170] Embodiments in which the lithium plating support is a porous and conductive but non-carbon material (e.g., copper, nickel, silicon, titanium, aluminum foil or foam). The substrate can be made more porous by acid etching (e.g., in HCl, HNO3 and / or HF, etc.) or by laser patterning to increase the lithium loading capacity. The non-carbon support material can also be alloyed with lithium prior to subsequent electroplating to reduce the formation of dendrites. The high intrinsic conductivity of these supports can also be converted into improved rate capability in the battery.

[0171] The lithium alloying kinetics in the above embodiments can be controlled by constant current (constant current) or constant potential (constant voltage). In the "anode-free" configuration of the assembled lithium-ion battery, constant current plating is most cautious. Its current density can be controlled at 0.1 mA / cm 2 Up to 0.5mA / cm 2 , 0.5mA / cm 2 Up to 1mA / cm 2 , 1mA / cm 2 Up to 2mA / cm 2 , 2mA / cm 2 Up to 3mA / cm 2 , 3mA / cm 2 Up to 4mA / cm 2 , or 4mA / cm 2 Up to 5mA / cm 2. Sometimes, it is more preferred to control the voltage for lithium plating alternatively, particularly when the resistance is high and / or when the electrodes are far apart. Some example voltages between two electrodes may include -0.1V to -0.5V, -0.5V to -1V, -1V to -2V, -2V to -3V, -3V to -4V, and -4V to -6V. The electrolyte used in these electroplating systems may include one or more lithium salts (e.g., LiPF6, LiFSI, LiTFSI, LiCl, LiBr, LiI, LiNO3, LiBOB, LiClO4, etc.) and concentrations of 0.1 mol to 0.5 mol, 0.5 mol to 1 mol, 1 mol to 2 mol, 2 mol to 3 mol, and 3 mol to 4 mol. In a solvent consisting of one or more anhydrous organic solvents (e.g., propylene carbonate, ethylene carbonate, diethyl carbonate, fluoroethylene carbonate, vinylene carbonate, 1,3-dioxolane, 1,2-dimethoxyethane, tetrahydrofuran, acetonitrile, etc.) or ionic liquids (e.g., 1-butyl-3-methylimidazolium hexafluorophosphate, 1-methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl)imide, N-ethyl-N-methylpyrrolidinium hydrofluoride, 1-ethyl-3-methyl-imidazolium bis(fluorosulfonyl)imide).

[0172] G. Surface modified lithium-silicon-carbon composite

[0173] In certain embodiments, the lithium-silicon-carbon composite particles include a modified surface, such as a coating or molecular bonding to the surface. Without being bound by theory, such modification may impart benefits such as enhanced electrochemical performance and enhanced safety of material handling, battery construction, and battery operation. The modification may be a coating and may at least partially cover the surface of the lithium-silicon-carbon composite.

[0174] In a preferred embodiment, the coating for the lithium-silicon alloy-carbon composite prevents any reaction with molecular oxygen, thereby providing stable storage and handling of the coated lithium-silicon-carbon composite in air. According to some embodiments, the carbonaceous layer is produced by CVD known in the art. According to other embodiments, the carbonaceous layer is produced by chemical vapor passivation (CVP) as disclosed in US2021 / 052995.

[0175] In certain embodiments, the surface layer may include a carbon layer. It is envisioned that the surface layer is to provide a suitable SEI layer. In this article, the surface carbon layer needs to be a good ion conductor for Li ion shuttle. Alternatively, the carbon layer may include an artificial SEI layer, for example, the carbon layer may include poly (3,4-ethylenedioxythiophene) -co (ethylene glycol) copolymer. The coating may include nitrogen and / or oxygen functional groups to further improve the layer related to the SEI layer that promotes stability. The coating needs to provide sufficient conductivity, adhesion and cohesion between particles. The surface should provide a stable SEI layer, which is generally composed of substances such as LiF, Li2CO3 and Li2O. Inorganic materials with relatively low bulk modulus can provide a more stable SEI layer, for example, preferably more amorphous relative to the crystalline layer, such as Li2CO3 relative to LiF.

[0176] To this end, a carbon layer can be applied to the lithium-silicon-carbon composite particles. Without being bound by theory, the carbon layer should provide a low surface area to provide a more stable SEI layer, higher first cycle efficiency and higher cycle stability in lithium-ion batteries. In the case of providing a surface layer for silicon-impregnated porous carbon materials (including graphite, graphene, hard carbon or soft carbon, such as pyrolytic carbon), various carbon allotropes can be envisioned.

[0177] In alternative embodiments, the coating can be achieved using a precursor solution known in the art followed by a carbonization process. For example, the particles can be coated by a wurster process known in the art or a related spray drying process to apply a thin layer of precursor material to the particles. The precursor coating can then be pyrolyzed, for example by further fluidizing the wurster-coated particles at elevated temperatures and in the presence of an inert gas, consistent with the description disclosed elsewhere herein.

[0178] In an optional embodiment, the particles can be covered in a carbonaceous layer realized by chemical vapor deposition (CVD). Without wishing to be bound by theory, it is believed that the CVD method of depositing a carbon layer (e.g., from a hydrocarbon gas) produces graphitizable carbon (also referred to as "soft" carbon in the art). The CVD method generally described in the art can be applied to the composite material disclosed herein. CVD is usually completed by subjecting the composite particle material to a period of time in the presence of a suitable deposition gas containing carbon atoms at an elevated temperature. In this article, suitable gases include but are not limited to methane, propane, butane, cyclohexane, ethane, propylene, ethylene and acetylene. The temperature can vary, for example, 350°C to 1050°C, for example, 350°C to 450°C, for example, 450°C to 550°C, for example, 550°C to 650°C, for example, 650°C to 750°C, for example, 750°C to 850°C, for example, 850°C to 950°C, for example, 950°C to 1050°C. In certain embodiments, the deposition gas is methane and the deposition temperature is greater than or equal to 950° C. In certain embodiments, the deposition gas is propane and the deposition temperature is less than or equal to 750° C. In certain embodiments, the deposition gas is cyclohexane and the deposition temperature is greater than or equal to 800° C. In certain embodiments, the deposition gas is acetylene and the deposition temperature is greater than or equal to 400° C. In certain embodiments, the deposition gas is ethylene and the deposition temperature is greater than or equal to 500° C. In certain embodiments, the deposition gas is propylene and the deposition temperature is greater than or equal to 400° C.

[0179] In certain embodiments, the coated reactor can be shaken in order to stir the lithium-silicon-carbon composite particles. In other exemplary modes, the particles can be fluidized, for example, impregnation with silicon-containing reactants can be carried out in a fluidized bed reactor. As known in the art, a variety of different reactor designs can be used herein, including but not limited to, lift kilns, roller kilns, rotary kilns, box kilns and improved fluidized bed designs.

[0180] The thickness of the carbon coating can vary, for example, from 1 nm to 2 nm, from 2 nm to 5 nm, from 5 nm to 10 nm, from 10 nm to 20 nm, from 20 nm to 50 nm, or from 50 nm to 100 nm. The mass percentage of the carbon coating on the lithium-carbon composite particles as a fraction of the total particle mass can vary, for example, from 0.01% to 0.1%, from 0.1% to 0.5%, from 0.5% to 1%, from 1% to 2%, from 2% to 5%, or greater than 5%. In an optional embodiment, the terminal carbon coating can be from 0.1% to 5%.

[0181] The composite material comprising lithium, silicon and carbon may also include a terminal coating that does not contain carbon. In some embodiments, such a non-carbon coating may be achieved by atomic layer deposition (ALD) as known in the art. The thickness of the ALD coating may vary, for example, from 1 nm to 2 nm, from 2 nm to 5 nm, from 5 nm to 10 nm, from 10 nm to 20 nm, from 20 nm to 50 nm, or from 50 nm to 100 nm. The mass percentage of the ceramic coating on the lithium-carbon composite particles may vary as a fraction of the total particle mass, for example, from 0.01% to 0.1%, from 0.1% to 0.5%, from 0.5% to 1%, from 1% to 2%, from 2% to 5%, or greater than 5%. Exemplary non-carbonaceous coatings in this regard include, but are not limited to, oxides comprising aluminum, oxides comprising zirconium, and oxides comprising titanium, and oxides comprising niobium. In an optional embodiment, the terminal ALD coating may be 0.1% to 5% (wt / wt).

[0182] Lithium-silicon-carbon composites can also be subjected to terminal carbon coating via hydrothermal carbonization, wherein the particles are treated by various modes according to the art. Hydrothermal carbonization can be completed in an aqueous environment at elevated temperatures and pressures. Examples of temperatures for completing hydrothermal carbonization vary, such as 150°C to 300°C, such as 170°C to 270°C, such as 180°C to 260°C, such as 200°C to 250°C. Alternatively, hydrothermal carbonization can be carried out at higher temperatures, such as 200°C to 800°C, such as 300°C to 700°C, such as 400°C to 600°C. In some embodiments, hydrothermal carbonization can be carried out at a temperature and pressure that achieves a graphite structure. The pressure range suitable for hydrothermal carbonization is known in the art, and the pressure can vary during the reaction, such as increasing. The pressure used for hydrothermal carbonization can vary from 0.1MPa to 200MPA. In certain embodiments, the pressure of hydrothermal carbonization is 0.5MPa to 5MPa. In other embodiments, the pressure of hydrothermal carbonization is 1MPa to 10MPa or 5MPa to 20MPa. In other embodiments, the pressure of hydrothermal carbonization is 10MPa to 50MPa. In other embodiments, the pressure of hydrothermal carbonization is 50MPa to 150MPa. In other embodiments, the pressure of hydrothermal carbonization is 100MPa to 200MPa. The raw material that is suitable as the carbon source of hydrothermal carbonization is also known in the art. This raw material for hydrothermal carbonization generally comprises carbon and oxygen, and these include but are not limited to the polymer precursor described elsewhere in sugar, oil, biological waste, polymer and the present disclosure.

[0183] H. Doping with electrochemical modifiers

[0184] In certain embodiments, the lithium-silicon-carbon composite material may be doped with a substance that achieves electrochemical property modification. Such electrochemical modifiers may provide enhanced electrochemical properties, including but not limited to increased capacitance, reduced resistance, increased storage stability, lithium metal dendrite inhibition, and increased cycling stability.

[0185] In some embodiments, electrochemical modifiers are used to inhibit lithium dendrite formation. As a result of continuous (and usually high-rate) lithium plating / stripping, lithium dendrite growth can lead to battery failure (sometimes catastrophic) due to the result of electrodes shorting together. Before reaching the plating voltage, porous carbon particles and / or electrodes decorated with nanometal seeds (e.g., Sn, Ni, In, Ag, Zn, Al, etc.) can be alloyed with lithium and / or form a low eutectic. This can inhibit dendrite formation by alleviating high local current areas and reducing the overpotential of lithium plating (and thereby reducing resistance). In certain related embodiments, the electrochemical modifier is a metal oxide, such as an oxide of Sn, Ni, In, Ag, Zn, Al, etc., or a combination thereof. In certain related embodiments, the electrochemical modifier includes a phosphate, such as a transition metal phosphate, an alkali metal phosphate, or a rare weathering metal phosphate.

[0186] In certain embodiments, the electrochemical modifier may act as a non-metallic dopant, such as oxygen, nitrogen, fluorine, chlorine, phosphorus, silicon, transition metals, etc. Without being bound by theory, the non-metallic dopant acts as an electronegative site to attract and grow lithium.

[0187] I. Physical and electrochemical properties of lithium-silicon-carbon composites

[0188] In certain embodiments, the lithium particles embedded in the composite include nanometer-sized features. The nanometer-sized features may have a characteristic length scale, such as less than 2nm, 2nm to 50nm, or greater than 50nm. In certain embodiments, the lithium-silicon alloy phase is embedded in the composite and includes nanometer-sized features. The nanometer-sized features may have a characteristic length scale, such as less than 2nm, 2nm to 50nm, or greater than 50nm.

[0189] The distribution of lithium and / or lithium-silicon alloy within the lithium-silicon-carbon composite can vary, for example, lithium and / or lithium-silicon alloy can be impregnated into the pores of porous carbon, wherein the fraction of the volume of the carbon interior voids filled can vary. For example, the percentage of lithium and / or lithium-silicon alloy filling within the total carbon pore volume can be 1% to 90%, such as 1% to 10%, 10% to 20%, 20% to 30%, 30% to 40%, 40% to 50%, 50% to 60%, 60% to 70%, 70% to 80%, or 80% to 90%. Alternatively, the percentage of lithium and / or lithium-silicon alloy filling within the total carbon pore volume can be 15% to 85%, such as 20% to 80%, 30% to 70%, or 40% to 60%.

[0190] The lithium domains may exist as a non-alloy phase, for example interspersed into the carbon skeleton structure, and / or the lithium domains may be completely surrounded by carbon. The geometry of the lithium domains within the carbon may vary, for example, may be spherical, cylindrical, or a zigzag structure. In some embodiments, the lithium exists as a layer coating the interior of the pores within the porous carbon scaffold.

[0191] The size of the impregnated lithium and / or lithium-silicon alloy can vary, for example, less than 2nm, 2nm to 5nm, 5nm to 10nm, 5nm to 20nm, 5nm to 30nm, 2nm to 50nm, 2nm to 30nm, 5nm to 50nm, 10nm to 100nm, 10nm to 150nm, 50nm to 150nm, 300nm to 1000nm, or 2nm to 1000nm.

[0192] Certain physicochemical and electrochemical properties of lithium-silicon carbon composites may vary. Some such properties are illustrated in Table 1.

[0193] Table 1. Embodiments of lithium carbon composite properties.

[0194]

[0195] *Measured in half-cell coin cells over a voltage range of 0.005 V to 0.8 V, cycled at C / 5 rate after first cycle at C / 10 rate, in carbonate solvent (EC:DEC 2:1 (w / w)) electrolyte containing 0.9M to 1.2M LiPF6 salt with additives such as FEC and / or VC present at 1% to 10% (w / w)

[0196] According to Table 1, the lithium-silicon-carbon composite material may include a combination of various properties. For example, the lithium-silicon-carbon composite material may include less than 100 m 2 / g surface area, greater than 80% first cycle efficiency and at least 1300mAh / g reversible capacity; or may include less than 100m 2 / g surface area, greater than 80% first cycle efficiency and at least 1600mAh / g reversible capacity; or may include less than 20m 2 / g surface area, greater than 85% first cycle efficiency and at least 1600mAh / g reversible capacity; or may include less than 10m 2 / g surface area, greater than 85% first cycle efficiency and at least 1600mAh / g reversible capacity; or may include less than 10m 2 / g surface area, greater than 90% first cycle efficiency and at least 1600mAh / g reversible capacity; or may include less than 10m 2 / g surface area, greater than 90% first cycle efficiency and at least 1800 mAh / g reversible capacity.

[0197] The lithium-carbon composite may include a combination of the above properties in addition to further including a carbon scaffold including the properties described herein. Accordingly, Table 2 provides a description of certain embodiments of combinations of properties of lithium-silicon-carbon composites.

[0198] Table 2. Embodiments of lithium-silicon-carbon composite properties.

[0199]

[0200] *Measured in half-cell coin cells over a voltage range of 0.005 V to 0.8 V, cycled at C / 5 rate after first cycle at C / 10 rate, in carbonate solvent (EC:DEC 2:1 (w / w)) electrolyte containing 0.9M to 1.2M LiPF6 salt with additives such as FEC and / or VC present at 1% to 10% (w / w)

[0201] As used herein, the percentages "microporosity", "mesoporosis" and "macroporosis" refer to the percentage of micropores, mesopores and macropores, respectively, as a percentage of the total pore volume. For example, a carbon scaffold having 90% microporosity is a carbon scaffold in which 90% of the total pore volume of the carbon scaffold is formed by micropores.

[0202] According to Table 2, the lithium-silicon-carbon composite may include a combination of various properties. For example, the lithium-silicon-carbon composite may include less than 100 m 2 / g surface area, greater than 85% first cycle efficiency, at least 1600mAh / g reversible capacity, 0.1% to 20% lithium content, 30% to 70% silicon content, 0.2cm 3 / g to 1.2cm 3 / g of the total pore volume of the carbon scaffold, wherein the scaffold pore volume comprises >80% micropores, <20% mesopores, and <10% macropores. For example, the lithium-silicon-carbon composite may comprise less than 20 m 2 / g surface area, greater than 85% first cycle efficiency, and at least 1600mAh / g reversible capacity, 0.1% to 20% lithium content, 30% to 70% silicon content, 0.2cm 3 / g to 1.2cm 3 / g of the total pore volume of the carbon scaffold, wherein the scaffold pore volume comprises >80% micropores, <20% mesopores, and <10% macropores. For example, the lithium-silicon-carbon composite may comprise less than 10 m 2 / g surface area, greater than 85% first cycle efficiency, and at least 1600mAh / g reversible capacity, 0.1% to 20% lithium content, 30% to 70% silicon content, 0.2cm 3 / g to 1.2cm 3 / g of the total pore volume of the carbon scaffold, wherein the scaffold pore volume comprises >80% micropores, <20% mesopores, and <10% macropores. For example, the lithium-silicon-carbon composite may comprise less than 10 m 2 / g surface area, greater than 90% first cycle efficiency, and at least 1600mAh / g reversible capacity, 0.1% to 20% lithium content, 30% to 70% silicon content, 0.2cm 3 / g to 1.2cm 3 / g of the total pore volume of the carbon scaffold, wherein the scaffold pore volume comprises >80% micropores, <20% mesopores, and <10% macropores. For example, the lithium-silicon-carbon composite may comprise less than 10 m 2 / g area, greater than 90% first cycle efficiency, and at least 1800mAh / g reversible capacity, 0.1% to 20% lithium content, 30% to 70% silicon content, 0.2cm 3 / g to 1.2cm 3 / g of the total pore volume of the carbon scaffold, wherein the scaffold pore volume includes >80% micropores, <20% mesopores and <10% macropores.

[0203] The lithium-silicon-carbon composite material may also include an inaccessible intra-particle void volume, such as a volume inaccessible to nitrogen. Thus, the lithium-carbon composite material may exhibit a relative humidity of less than 2.1 g / cm 3 , for example, less than 2.0 g / cm 3 , for example, less than 1.9 g / cm 3 , for example, less than 1.8 g / cm 3 , for example, less than 1.7 g / cm 3 , for example, less than 1.6 g / cm 3 , for example, less than 1.4 g / cm 3 , for example, less than 1.2 g / cm 3 , for example, less than 1.0 g / cm 3 Pycnometer density.

[0204] In some embodiments, the lithium-silicon-carbon composite material can exhibit a relative humidity of 1.7 g / cm 3 Up to 2.1g / cm 3 , for example 1.7 g / cm 3 Up to 1.8g / cm 3 , 1.8g / cm 3 Up to 1.9g / cm 3 , for example 1.9g / cm 3 Up to 2.0g / cm 3 , for example 2.0g / cm 3 Up to 2.1g / cm 3 In some embodiments, the lithium-silicon carbon composite material can exhibit a pycnometer density of 1.8 g / cm 3 Up to 2.1g / cm 3 In some embodiments, the lithium-silicon carbon composite material can exhibit a pycnometer density of 1.8 g / cm 3 Up to 2.0g / cm 3 In some embodiments, the lithium-carbon composite material may exhibit a pycnometer density of 1.9 g / cm 3 Up to 2.1g / cm 3 Pycnometer density.

[0205] The pore volume of the lithium-silicon-carbon composite material that exhibits extremely durable lithium insertion can be 0.01 cm 3 / g to 0.2cm 3 In some embodiments, the pore volume of the lithium-silicon carbon composite material can be 0.01 cm 3 / g to 0.15cm 3 / g, for example 0.01cm 3 / g to 0.1cm 3 / g, for example 0.01cm 3 / g to 0.05cm 3 / g.

[0206] The particle size distribution of lithium-silicon-carbon composite is important for determining power performance and volume capacity. With the improvement of filler, volume capacity can be increased. In some embodiments, particle size distribution is a Gaussian distribution with a unimodal shape. In other embodiments, particle size distribution includes multiple modes, such as bimodal or multimodal (>2 different peaks, such as trimodal). Particle size distribution can have a right skew. In other embodiments, particle size distribution can have a left skew. The particle size properties of the composite can be described by volume particle size distribution, such as Dv1, Dv10, Dv50, Dv90, Dv99 known in the art. The best combination of particle filling and performance will be some combinations of the following size ranges. The particle size reduction in this embodiment can be carried out as known in the art, for example, by jet milling in the presence of various gases (including air, nitrogen, argon, helium, supercritical steam and other gases known in the art).

[0207] In one embodiment, the Dv1 of the composite material can be 1 nm to 5 microns. In another embodiment, the Dv1 of the composite is 5 nm to 1 micron, such as 5 nm to 500 nm, such as 5 nm to 100 nm, such as 10 nm to 50 nm. In another embodiment, the Dv1 of the composite is 500 nm to 2 microns, or 750 nm to 1 μm, or 1 μm to 2 μm, microns to 2 microns. In other embodiments, the Dv1 of the composite is 2 μm to 5 μm, or >5 μm. In preferred embodiments, Dv1<5 μm or Dv1<3 μm, Dv1<2 μm, Dv1<1.5 μm.

[0208] The Dv10 of the composite material may be 1 nm to 10 μm. In preferred embodiments, Dv10<10 μm or Dv10<8 μm, Dv10<6 μm, Dv10<5 μm, Dv10<4 μm, Dv10<3 μm, Dv10<2 μm.

[0209] In some embodiments, the Dv50 of the composite material is 5nm to 20μm. In other embodiments, the Dv50 of the composite is 5nm to 1μm, such as 5nm to 500nm, such as 5nm to 100nm, such as 10nm to 50nm. In another embodiment, the Dv50 of the composite is 500nm to 2μm, 750nm to 1μm, 1μm to 2μm. In other embodiments, the Dv50 of the composite is 1μm to 1000μm, such as 1μm to 100μm, such as 1μm to 10μm, such as 2μm to 20μm, such as 3μm to 15μm, such as 4μm to 8μm. In certain embodiments, Dv50>20μm, such as>50μm, such as>100μm.

[0210] The Dv90 of the composite material may be from 1 μm to 50 μm. In preferred embodiments, the Dv90 is from 1 μm to 30 μm, from 2 μm to 25 μm, from 3 μm to 20 μm, from 4 μm to 20 μm, from 5 μm to 20 μm, from 6 μm to 20 μm, from 8 μm to 20 μm, from 10 μm to 20 μm, or from 15 μm to 20 μm. In other embodiments, the Dv90 is less than 50 μm, less than 40 μm, less than 30 μm, less than 20 μm, or less than 15 μm.

[0211] The Dv99 of the composite material can be 1 μm to 50 μm. In preferred embodiments, the Dv90 is 1 μm to 30 μm, 2 μm to 25 μm, 3 μm to 25 μm, 4 μm to 25 μm, 5 μm to 25 μm, 6 μm to 20 μm, 8 μm to 20 μm, 10 μm to 20 μm, or 15 μm to 25 μm. In other embodiments, the Dv90 is less than 50 μm, less than 40 μm, less than 30 μm, less than 20 μm, or less than 15 μm.

[0212] The span (Dv90-Dv10) / (Dv50) (where Dv10, Dv50, and Dv90 represent the particle sizes at 10%, 50%, and 90% of the volume distribution) can vary from, for example, 100 to 10, 10 to 5, 5 to 2, 2 to 1; in some embodiments, the span can be less than 1. In certain embodiments, the composite material comprises a unimodal particle size distribution. In certain embodiments, the composite material particle size distribution has a right skewness. In certain embodiments, the composite material particle size distribution has a left skewness. In certain embodiments, the composite material particle size distribution can be multimodal, such as bimodal or trimodal.

[0213] The surface functionality of the composite materials currently disclosed that exhibit extremely durable lithium intercalation can be varied to obtain desired electrochemical properties. One property that can predict surface functionality is the pH of the composite material. The composite materials disclosed herein include pH values ​​of less than 1 to about 14, such as less than 5, 5 to 8, or greater than 8. In some embodiments, the pH of the composite material is less than 4, less than 3, less than 2, or even less than 1. In other embodiments, the pH of the composite material is about 5 to 6, about 6 to 7, about 7 to 8, or 8 to 9, or 9 to 10. In other embodiments, the pH of the composite material is high and the pH range is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.

[0214] The composite material may contain varying amounts of carbon, oxygen, hydrogen, and nitrogen as measured by gas chromatography CHNO analysis. In one embodiment, the carbon content of the composite is greater than 98 wt.% or even greater than 99.9 wt.%, as measured by CHNO analysis. In another embodiment, the carbon content of the lithium-carbon composite is about 10% to 90%, such as 20% to 80%, such as 30% to 70%, such as 40% to 60%.

[0215] In some embodiments, the composite material comprises a nitrogen content of 0 to 90%, such as 0.1% to 1%, such as 1% to 3%, such as 1% to 5%, such as 1% to 10%, such as 10% to 20%, such as 20% to 30%, such as 30% to 90%.

[0216] In some embodiments, the composite material comprises an oxygen content of 0 to 90%, such as 0.1% to 1%, such as 1% to 3%, such as 1% to 5%, such as 1% to 10%, such as 10% to 20%, such as 20% to 30%, such as 30% to 90%.

[0217] The morphology of the carbon scaffold particles can vary. For example, the carbon scaffold particles are spherical in shape.

[0218] Composite material can also be mixed with electrochemical modifier, and electrochemical modifier is selected to optimize the electrochemical performance of unmodified composite.Electrochemical modifier can be mixed into pore structure and / or on the surface of porous carbon support, embedded in lithium or final carbon layer or conductive polymer, coating, or mixed in any number of other ways.For example, in some embodiments, composite material includes electrochemical modifier (for example, lithium or Al2O3) coating on the surface of carbon material.In some embodiments, composite material includes electrochemical modifier greater than about 100ppm.In certain embodiments, electrochemical modifier is selected from iron, tin, nickel, aluminum and manganese.

[0219] In certain embodiments, the electrochemical modifier comprises an element (e.g., silicon, tin, sulfur) that has the ability to be lithiated from 3V to 0V relative to lithium metal. In other embodiments, the electrochemical modifier comprises a metal oxide (e.g., iron oxide, molybdenum oxide, titanium oxide) that has the ability to be lithiated from 3V to 0V relative to lithium metal. In other embodiments, the electrochemical modifier comprises an element (e.g., aluminum, manganese, nickel, metal phosphate) that is not lithiated from 3V to 0V relative to lithium metal. In other embodiments, the electrochemical modifier comprises a non-metallic element (e.g., fluorine, nitrogen, hydrogen). In other embodiments, the electrochemical modifier includes any one of the aforementioned electrochemical modifiers or any combination thereof (e.g., tin-silicon, nickel-titanium oxide).

[0220] The electrochemical modifier can be provided in any form. For example, in some embodiments, the electrochemical modifier comprises a salt. In other embodiments, the electrochemical modifier comprises one or more elements in elemental form, such as elemental iron, tin, silicon, nickel, or manganese. In other embodiments, the electrochemical modifier comprises one or more elements in oxidized form, such as iron oxide, tin oxide, silicon oxide, nickel oxide, aluminum oxide, or manganese oxide.

[0221] The electrochemical performance of the composite material can be modified at least in part by the amount of electrochemical modifier in the material, wherein the electrochemical modifier is an alloy material, such as silicon, tin, indium, aluminum, germanium, gallium. Thus, in some embodiments, the composite material comprises at least 0.10%, at least 0.25%, at least 0.50%, at least 1.0%, at least 5.0%, at least 10%, at least 25%, at least 50%, at least 75%, at least 90%, at least 95%, at least 99%, or at least 99.5% of the electrochemical modifier.

[0222] It is anticipated that in certain embodiments, the composite material will include a portion of trapped pore volume, i.e., void volume that is inaccessible to nitrogen as detected by nitrogen adsorption measurements. Without being bound by theory, this trapped pore volume is important because it provides volume into which silicon can expand upon lithiation. Internal void volume can be determined by various methods, such as by pycnometer density and / or tapped density.

[0223] In certain embodiments, the percentage volume of the inaccessible void volume relative to the total volume of the composite particle varies from 0.1% to 90%, e.g., 5% to 85%, 10% to 70%, 20% to 60%, 20% to 50%, 20% to 40%, or 30% to 40%.

[0224] In certain embodiments, the electrochemical performance of the composite disclosed herein is tested in a half-cell; alternatively, the performance of the composite is tested in a full cell, such as a full cell button cell, a full cell pouch cell, a square storage battery, or other battery configurations known in the art. The anode composition including the composite material may also include various substances known in the art. Other formulation components include but are not limited to conductive additives (e.g., conductive carbon, such as super C45, super P, Ketjen black, etc.), conductive polymers, etc., adhesives (e.g., styrene-butadiene rubber sodium carboxymethyl cellulose (SBR-Na-CMC), polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), etc.) and combinations thereof. In certain embodiments, the adhesive may include lithium ions as counter ions (e.g., lithium polyacrylate (LiPAA), lithium carboxymethyl cellulose (Li-CMC), etc.).

[0225] Other species including electrodes are known in the art. The weight percentage of active material in the electrode can be, for example, 1% to 5%, for example, 5% to 15%, for example, 15% to 25%, for example, 25% to 35%, for example, 35% to 45%, for example, 45% to 55%, for example, 55% to 65%, for example, 65% to 75%, for example, 75% to 85%, for example, 85% to 95%. In some embodiments, the active material accounts for 80% to 95% of the electrode. In certain embodiments, the amount of the conductive additive in the electrode can vary, for example, 1% to 5%, for example, 5% to 15%, for example, 15% to 25%, for example, 25% to 35%. In some embodiments, the amount of the conductive additive in the electrode is 5% to 25%. In certain embodiments, the amount of the binder can vary, for example, 1% to 5%, for example, 5% to 15%, for example, 15% to 25%, for example, 25% to 35%. In certain embodiments, the amount of the conductive additive in the electrode is 5% to 25%.

[0226] Anodes comprising lithium-silicon-carbon composites can be paired with various cathode materials to obtain full-cell lithium-silicon batteries. Examples of suitable cathode materials are known in the art. Examples of such cathode materials include, but are not limited to, LiCoO2 (LCO), LiNi 0.8 Co 0.15 Al 0.05 O2(NCA), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC), LiNi 0.5 Mn 1.5 O4 (LNMO), LiMn2O4 and variants (LMO), LiFePO4 (LFP), FeF2, CuF2 and S.

[0227] For batteries including lithium-silicon-carbon composites, the cathode to anode pairing ratio can be varied, where the ratio is based on the capacity cathode to the capacity anode, for example in units of Ah cathode to Ah anode, or in units of Ah / cm 2 Cathode ratio Ah / cm 2 The ratio of cathode to anode capacity can vary from 0.7 to 1.3. In certain embodiments, the ratio of cathode to anode capacity can vary from 0.7 to 1.0, such as 0.8 to 1.0, such as 0.85 to 1.0, such as 0.9 to 1.0, such as 0.95 to 1.0. In other embodiments, the ratio of cathode to anode capacity can vary from 1.0 to 1.3, such as 1.0 to 1.2, such as 1.0 to 1.15, such as 1.0 to 1.1, such as 1.0 to 1.05. In other embodiments, the ratio of cathode to anode capacity can vary from 0.8 to 1.2, such as 0.9 to 1.1, such as 0.95 to 1.05.

[0228] In a preferred embodiment, for a battery comprising a lithium-silicon-carbon composite, the pairing of the cathode to the anode is less than 1.00 and the first cycle efficiency is greater than 80%, for example greater than 85%, for example greater than 90%, for example greater than 91%, for example greater than 92%, for example greater than 93%, for example greater than 94%, for example greater than 95%, for example greater than 96%, for example greater than 97%, for example greater than 98%, for example greater than 99%.

[0229] For a full-cell lithium-silicon battery comprising a lithium-silicon-carbon composite, the voltage window for charging and discharging can be changed. In this regard, the voltage window can be varied as known in the art. For example, the choice of cathode as known in the art works in the selected voltage window. Examples of voltage windows vary, for example, from 2.0V to 5.0V, for example, 2.5V to 4.5V, for example, 2.5V to 4.2V relative to the potential of Li / Li+. In such an embodiment, the plating voltage (charging of the battery) of the lithium-carbon composite anode is 0 to -100mV, for example, 0 to -50mV, for example, 0 to -40mV, for example, 0 to -30mV, for example, 0 to -20mV, for example, 0 to -10mV, for example, 0 to -5mV, for example, 0 to -1mV.

[0230] In order to evaluate the ability of the lithium-silicon-carbon anode to suppress lithium dendrite formation upon constant current charge / discharge cycling, the performance of a half-cell having a lithium metal foil as a counter electrode and a lithium carbon composite as an active material contained within a working electrode can be evaluated. Specifically, electrochemical testing of the half-cell includes constant current charge / discharge cycling with the desired result of minimizing or eliminating short circuits due to lithium dendrite formation.

[0231] For full-cell lithium-silicon batteries comprising lithium-silicon-carbon composites, the strategy for conditioning the battery can vary as known in the art. For example, conditioning can be accomplished by one or more charge and discharge cycles at various rates (e.g., at a rate slower than the desired cycle rate). As known in the art, the conditioning process can also include the steps of opening the lithium-ion battery, evacuating any gases generated during the conditioning process, and then resealing the lithium-ion battery.

[0232] For lithium silicon carbon batteries comprising lithium-silicon-carbon composites, the cycle rate can vary as known in the art, for example, the rate can be C / 20 to 20C, such as C10 to 10C, such as C / 5 to 5C. In certain embodiments, the cycle rate is C / 10. In certain embodiments, the cycle rate is C / 5. In certain embodiments, the cycle rate is C / 2. In certain embodiments, the cycle rate is 1C. In certain embodiments, the cycle rate is 1C, wherein the rate is periodically reduced to a slower rate, such as cycling at 1C at a C / 10 rate adopted every 20th cycle. In certain embodiments, the cycle rate is 2C. In certain embodiments, the cycle rate is 4C. In certain embodiments, the cycle rate is 5C. In certain embodiments, the cycle rate is 10C. In certain embodiments, the cycle rate is 20C.

[0233] In certain embodiments, the electrolyte may include various additives known to provide improved performance, such as fluoroethylene carbonate (FEC) or other related fluorocarbonate compounds, or ester co-solvents (such as methyl butyrate, vinylene carbonate), and other electrolyte additives known to improve electrochemical performance.

[0234] When tested in a half-cell, the coulombic efficiency of the lithium-silicon-carbon composite can be averaged, for example, averaged after cycle 5 or more. In certain embodiments, the average efficiency of the extremely durable lithium intercalation composite is greater than 0.9, or 90%. In certain embodiments, the average efficiency is greater than 0.95 or 95%. In certain other embodiments, the average efficiency is 0.99 or greater, such as 0.991 or greater, such as 0.992 or greater, such as 0.993 or greater, such as 0.994 or greater, such as 0.995 or greater, such as 0.996 or greater, such as 0.997 or greater, such as 0.998 or greater, such as 0.999 or greater, such as 0.9991 or greater, such as 0.9992 or greater, such as 0.9993 or greater, such as 0.9994 or greater, such as 0.9995 or greater, such as 0.9996 or greater, such as 0.9997 or higher, such as 0.9998 or higher, such as 0.9999 or higher.

[0235] In order to measure the relative amount of silicon impregnated into the porosity of the porous carbon, thermogravimetric analysis (TGA) can be used. TGA can be used to evaluate the proportion of silicon present in the porosity of the porous carbon relative to the proportion of the total silicon content, that is, the sum of silicon in the porosity and on the surface of the particles. When the silicon-carbon composite is heated in air, the sample begins to show a mass increase at about 300°C to 500°C, which reflects the initial oxidation of silicon to SiO2, and then the sample shows a mass loss as the carbon burns off, and then the sample shows a mass increase, which reflects the recovery conversion of silicon to SiO2, as the temperature approaches 1100°C, silicon oxidation is completed, and the mass increase tends to an asymptotic value. For the purpose of this analysis, it is assumed that the minimum mass recorded when the sample is heated from 800°C to 1100°C represents the point where carbon combustion is completed. Any further mass increase beyond this point corresponds to the oxidation of silicon to SiO2, and the total mass at the completion of oxidation is SiO2. Therefore, the percentage of unoxidized silicon after carbon combustion as a proportion of the total amount of silicon can be determined using the following formula:

[0236] Z=1.875x[(M1100-M) / M1100]x 100

[0237] where M1100 is the mass of the sample when oxidation is completed at a temperature of 1100 °C, and M is the minimum mass recorded when the sample is heated from 800 °C to 1100 °C.

[0238] Without being bound by theory, under TGA conditions, the temperature at which silicon oxidizes is related to the length scale of the oxide coating on silicon due to the diffusion of oxygen atoms through the oxide layer. Therefore, silicon present within the carbon pores will oxidize at a lower temperature than silicon deposited on the particle surface, since the coating present on these surfaces is necessarily thinner. In this way, the calculation of Z is used to quantitatively assess the fraction of silicon that is not impregnated within the pores of the porous carbon scaffold.

[0239] In preferred embodiments, Z is less than 30, Z is less than 20, Z is less than 15, Z is less than 10, Z is less than 5, Z is less than 4, Z is less than 3, Z is less than 2, Z is less than 1, or Z is less than 0.1. This preferred level of Z can be combined with other properties of the lithium-silicon-carbon composite, such as one, several or all of the properties shown in Table 1. Alternatively, this preferred level of Z can be combined with one, several or all of the properties shown in Table 2.

[0240] Example

[0241] Example 1. Properties of various carbon scaffold materials. The properties of various carbon scaffold materials are shown in Table 3. Exemplary carbon materials have properties such as total pore volume (e.g., from 0.5 cm 3 / g changes to greater than 2cm 3 / g, and different percentages of micropores, mesopores and macropores).

[0242] Table 3. Properties of various carbon scaffold materials.

[0243]

[0244] Example 2. Particle size distribution of various carbon scaffold materials. The particle size distribution of various carbon scaffold materials was determined by using a laser diffraction particle size analyzer known in the art. Table 4 gives the data, especially Dv1, Dv10, Dv50 and Dv90 and Dv100.

[0245] Table 4. Properties of various carbon scaffold materials.

[0246]

[0247] Example 3. Production of silicon-carbon composites by CVI. Using carbon support 1, silicon-carbon composites (silicon-carbon composite 1) were produced by CVI as follows. Amorphous porous carbon with a mass of 0.2 grams was placed in a 2-inch × 2-inch ceramic crucible and then placed in the center of a horizontal tube furnace. The furnace was sealed and purged continuously with nitrogen at 500 cubic centimeters per minute (ccm). The temperature of the furnace was raised to a peak temperature of 450°C at 20°C / min, and it was allowed to balance for 30 minutes at this peak temperature. At this point, nitrogen was turned off, and silane and hydrogen were then introduced at flow rates of 50ccm and 450ccm, respectively, for a total residence time of 30 minutes. After the residence period, silane and hydrogen were turned off, and nitrogen was introduced into the furnace again to purge the internal atmosphere. At the same time, the furnace heat was turned off and allowed to cool to ambient temperature. The completed silicon-carbon material was then taken out of the furnace. This same CVI process can be completed for lithium-carbon composites or porous carbon skeletons containing lithium precursors.

[0248] Example 4. Analysis of various composite materials. Various silicon-carbon composite materials were produced using the CVI method using the carbon support samples described in Tables 3 and 4 in the static bed configuration generally described in Example 3. These silicon-carbon samples were prepared using a range of process conditions: silane concentrations from 1.25% to 100%, diluent gases nitrogen or hydrogen, and carbon support starting masses from 0.2 g to 700 g. Similar production strategies can be accomplished for CVI treatment of lithium-carbon composites or porous carbon frameworks containing lithium precursors.

[0249] The surface area of ​​the silicon-carbon composite is determined. The silicon-carbon composite is also analyzed by TGA to determine the silicon content and Z. The silicon-carbon composite is also tested in a half-cell button cell. The anode for the half-cell button cell may include 60% to 90% silicon-carbon composite, 5% to 20% Na-CMC (as a binder) and 5% to 20% super C45 (as a conductivity enhancer), and the electrolyte may include 2:1 ethylene carbonate: diethyl carbonate, 1M LiPF6 and 10% fluoroethylene carbonate. The half-cell button cell can be cycled for 5 cycles at a rate of C / 5 at 25°C and then cycled at a rate of C / 10. The voltage can be cycled from 0V to 0.8V, and alternatively, the voltage can be cycled from 0V to 1.5V. According to the half-cell button cell data, the maximum capacity and the average coulombic efficiency (CE) in the cycle range from cycle 7 to cycle 20 can be measured. The physicochemical and electrochemical properties of various silicon-carbon composites are shown in Table 5.

[0250] Table 5. Properties of various silicon-carbon materials.

[0251]

[0252] From these data, it can be seen that the average Coulombic efficiency increases significantly for silicon-carbon samples with low Z. In particular, all silicon-carbon samples with Z below 10.0 exhibit an average Coulombic efficiency of > 0.9941, and all silicon-carbon samples with Z higher than 10 (silicon-carbon composite sample 12 to silicon-carbon composite sample 16) were observed to have < The average coulombic efficiency of 0.9909. Without being bound by theory, the higher coulombic efficiency of the silicon-carbon samples with Z < 10 provides excellent cycling stability in full-cell lithium-ion batteries. Further investigation of the table reveals the surprising and unexpected discovery that the combination of silicon-carbon composite samples with Z < 10 and also containing a carbon scaffold with a microporosity of > 69.1 provides > Average Coulombic efficiency of 0.9969.

[0253] Therefore, in a preferred embodiment, the lithium-silicon-carbon composite material comprises less than 10 Z, such as less than 5 Z, such as less than 3 Z, such as less than 2 Z, such as less than 1 Z, such as less than 0.5 Z, such as less than 0.1 Z, or zero Z. This preferred content of Z can be combined with other properties of the lithium-silicon-carbon composite, such as one, several or all of the properties shown in Table 1. Alternatively, this preferred content of Z can be combined with one, several or all of the properties shown in Table 2.

[0254] Example 5. Method for preparing a lithium-silicon-carbon composite by melt intrusion into porous carbon followed by CVI. Porous carbon particles are placed in a metal or ceramic crucible and physically mixed with a portion of lithium metal in foil or powder form. The Li:C weight ratio is adjusted so as to partially fill the available pore volume of the carbon, allowing some residual voids (e.g., 0.01w / w Li:C, 0.02w / w Li:C, 0.05w / w Li:C, 0.1w / w Li:C, 0.2w / w Li:C, 0.3w / w Li:C, 0.4w / w Li:C or 0.5w / w Li:C). The mixture is then heated to at least the melting point of lithium metal (e.g., 180°C, 190°C, 200°C, 220°C, 250°C, 300°C, 400°C, etc.) in an inert atmosphere (e.g., argon, nitrogen, helium or vacuum). The mixture is left at the peak temperature for a period of time (e.g., 0.1 hour, 1 hour, 2 hours, 5 hours, 10 hours, 24 hours, etc.) to allow the molten lithium to penetrate the carbon pore structure via capillary forces. A lithium-carbon composite is formed at this point, which is then cooled to ambient temperature and taken out for processing. The lithium present in the lithium-carbon composite can be reduced as generally described in the present disclosure. The lithium-carbon composite can be further processed via CVI to incorporate silicon into one or more holes of the porous carbon skeleton.

[0255] In another embodiment, the lithium metal and porous carbon powder are kept separate in the same heated reactor environment, and the temperature is heated hotter to increase the vapor pressure of the molten lithium (e.g., 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1350°C, etc.). This will promote the vapor deposition of lithium metal within the pore structure of the carbon via capillary condensation. Thus, the Li:C ratio will be controlled by the residence time at the peak temperature (e.g., 0.1 hour, 1 hour, 2 hours, 5 hours, 10 hours, 24 hours, etc.).

[0256] In another embodiment, the lithium metal source is in the form of an electrode / target for a plasma physical vapor deposition apparatus, and porous carbon is used as a counter electrode. The synthesis is performed by applying a bias voltage between the electrodes under a partial pressure of argon. This promotes evaporation of lithium metal via ion bombardment, resulting in lithium metal deposition occurring on the porous carbon. The deposition rate can be controlled by the applied bias voltage and current. The Li:C ratio can be controlled by a residence time similar to the above embodiment.

[0257] Example 6. A method for preparing a melt-intrusion lithium-silicon-carbon composite into a silicon-carbon composite. The silicon-carbon composite particles are placed in a metal or ceramic crucible and physically mixed with a portion of lithium metal in foil or powder form. The weight ratio of Li: silicon-carbon composite is adjusted so as to partially fill the available pore volume of the carbon, allowing some residual voids (e.g., 0.01w / w Li: silicon-carbon composite, 0.02w / w Li: silicon-carbon composite, 0.05w / w Li: silicon-carbon composite, 0.1w / w Li: silicon-carbon composite, 0.2w / w Li: silicon-carbon composite, 0.3w / w Li: silicon-carbon composite, 0.4w / w Li: silicon-carbon composite, or 0.5w / w Li: silicon-carbon composite). The mixture is then heated to at least the melting point of lithium metal (e.g., 180°C, 190°C, 200°C, 220°C, 250°C, 300°C, 400°C, etc.) in an inert atmosphere (e.g., argon, nitrogen, helium, or vacuum). The mixture is held at the peak temperature for a period of time (e.g., 0.1 hour, 1 hour, 2 hours, 5 hours, 10 hours, 24 hours, etc.) to allow the molten lithium to penetrate the carbon pore structure via capillary forces. At this point, a lithium-silicon-carbon composite is formed, which is then cooled to ambient temperature and removed for processing.

[0258] In another embodiment, the lithium metal and silicon-carbon composite are kept separate in the same heated reactor environment, and the temperature is heated even hotter to increase the vapor pressure of the molten lithium (e.g., 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1350°C, etc.). This will promote the vapor deposition of lithium metal within the pore structure of the carbon via capillary condensation. Thus, the Li:C ratio will be controlled by the residence time at the peak temperature (e.g., 0.1 hour, 1 hour, 2 hours, 5 hours, 10 hours, 24 hours, etc.).

[0259] In another embodiment, the lithium metal source is in the form of an electrode / target for a plasma physical vapor deposition apparatus, and porous carbon is used as a counter electrode. The synthesis is performed by applying a bias voltage between the electrodes under a partial pressure of argon. This promotes evaporation of lithium metal via ion bombardment, resulting in lithium metal deposition occurring on the porous carbon. The deposition rate can be controlled by the applied bias voltage and current. The Li:C ratio can be controlled by a residence time similar to the above embodiment.

[0260] Lithium present in the lithium-silicon-carbon composite may be reduced as generally described in this disclosure.

[0261] Embodiment 7. is used for the method that the solution of synthesis lithium-silicon-carbon composite is invaded into porous carbon skeleton.In typical embodiment, the solution of naphthalene in anhydrous non-protonic ether solvent (for example, tetrahydrofuran, dimethoxyethane, diethyl ether, etc.) is prepared in inert gas environment (for example, argon, nitrogen, helium, etc.).While stirring or ultrasonic treatment, a portion of lithium metal (with naphthalene molar ratio of 1: 1) is added to the solution in the form of foil, pellets or powder.Lithium metal is completely dissolved into transparent green solution.Porous carbon is then added to the solution with required Li:C ratio, as shown in Example 5.Thereafter, solvent exchange with non-ether non-protonic solvent (for example, toluene, acetonitrile, etc.) is followed by evaporation to remove solvent and naphthalene from the mixture, produce dry lithium-carbon composite material, then the dry lithium-carbon composite material can be removed to be treated via silane CVI, produce lithium-silicon-carbon composite material.Before CVI process, lithium present in lithium-carbon composite material can be reduced as generally described in the present disclosure.

[0262] In another preferred embodiment, the mixture is then heated to a temperature to promote evaporation of both naphthalene and the solvent species (e.g., >220° C.). Only the lithium-carbon composite material is left and the use of additional solvent is abandoned. This lithium-carbon composite as discussed for this embodiment can then be further processed via silicon CVI according to the procedures generally described herein to produce a lithium-silicon-carbon composite, and the lithium present in the lithium-silicon-carbon composite can be reduced as generally described in the present disclosure.

[0263] Embodiment 8. is used for the method that the solution of synthesis lithium-silicon-carbon composite is invaded into silicon-carbon composite.In typical embodiment, the solution of naphthalene in anhydrous aprotic ether solvent (for example, tetrahydrofuran, dimethoxyethane, diethyl ether, etc.) is prepared in an inert gas environment (for example, argon, nitrogen, helium, etc.).While stirring or ultrasonic treatment, a portion of lithium metal (with naphthalene molar ratio of 1: 1) is added to the solution in the form of foil, pellets or powder.The lithium metal is completely dissolved into a transparent green solution.Then the silicon-carbon composite produced by CVI is added to the solution with the required Li:C ratio, as shown in Example 6. Subsequently, the solvent and naphthalene are removed from the mixture by solvent exchange with a non-ether aprotic solvent (for example, toluene, acetonitrile, etc.) and then evaporated to produce a dry lithium-carbon composite material.

[0264] In another preferred embodiment, the mixture is then heated to a temperature to promote evaporation of both naphthalene and the solvent species (eg, >220° C.), leaving only the lithium-carbon composite material and forgoing the use of additional solvent.

[0265] Lithium present in the lithium-silicon-carbon composite may be reduced as generally described in this disclosure.

[0266] Example 9. Gas phase synthesis method for lithium-carbon composites. Lithium is produced in the pores of a porous carbon support by subjecting porous carbon particles to a lithium-containing precursor gas and elevated temperatures to achieve lithium chemical vapor infiltration (CVI). For example, the elevated temperature is above the boiling point of the lithium-containing precursor to achieve its gasification. In this regard, exemplary lithium precursors include, but are not limited to, lithium bis(trimethylsilyl)amide, lithium acetylsalicylate, lithium amide, lithium bromide, lithium borohydride, lithium chloride, lithium hydride, and lithium hydroxide, and mixtures thereof. The lithium-containing precursor gas may be mixed with other inert gases, for example, nitrogen, or hydrogen, or argon, or helium, or a combination thereof.

[0267] The temperature and time of the treatment can vary, for example, the temperature can be 50°C to 900°C, such as 50°C to 250°C, such as 50°C to 100°C, such as 75°C to 150°C, such as 100°C to 150°C, such as 150°C to 200°C, such as 200°C to 250°C, such as 250°C to 300°C, such as 300°C to 350°C, such as 300°C to 400°C, such as 350°C to 450°C, such as 350°C to 400°C, such as 400°C to 500°C, such as 500°C to 600°C, such as 600°C to 700°C, such as 700°C to 800°C, such as 800°C to 900°C, such as 600°C to 1100°C.

[0268] The gas mixture may contain 0.1% to 1% of a gaseous lithium precursor and the remaining inert gas. Alternatively, the gas mixture may contain 1% to 10% of a lithium precursor and the remaining inert gas. Alternatively, the gas mixture may contain 10% to 20% of a lithium precursor and the remaining inert gas. Alternatively, the gas mixture may contain 20% to 50% of a lithium precursor and the remaining inert gas. Alternatively, the gas mixture may contain greater than 50% of a lithium precursor and the remaining inert gas. Alternatively, the gas may be substantially 100% lithium precursor gas. The pressure of the CVI process may vary. In some embodiments, the pressure is atmospheric pressure. In some embodiments, the pressure is below atmospheric pressure. In some embodiments, the pressure is above atmospheric pressure. Then, such a lithium-carbon composite as discussed for this embodiment may be further processed via silicon CVI according to the methods generally described herein to produce a lithium-silicon-carbon composite.

[0269] In a related embodiment, lithium is added to the silicon-carbon composite particles by subjecting the silicon-carbon composite particles to a lithium-containing precursor gas and elevated temperatures to effect lithium chemical vapor infiltration (CVI).

[0270] Lithium chemical vapor infiltration (CVI) is achieved by subjecting the porous carbon particles to a lithium-containing precursor gas and elevated temperature within the porous carbon support. For example, the elevated temperature is above the boiling point of the lithium-containing precursor to achieve its vaporization.

[0271] Example 10. Addition of alloying substances for synthesizing lithium carbon composites. As known in the art, lithium metal can be alloyed with other elements in some cases to form low melting point (<180°C) eutectic mixtures. These low eutectic mixtures can be used to more easily guide the formation / precipitation of lithium metal within the porous carbon structure. In one such embodiment, the porous carbon scaffold is first loaded with an alloying agent (e.g., silver) in the form of a solution (e.g., 0.1M silver nitrate in water) containing an alloy precursor. The solution is added to the dry porous carbon powder at a low relative concentration (e.g., 0.1% w / w Ag:C, 1% w / w Ag:C, 2% w / w Ag:C, 5% w / w Ag:C, or 10% w / w Ag:C) via a technique known in the art as the initial wetness method. The aqueous solvent is then removed via evaporation, and the alloy precursor is decomposed / reduced to its metallic neutral oxidation state (i.e., silver metal) throughout the pore structure of the carbon in the form of discrete nanoparticles (e.g., 1nm to 50nm in diameter). The Ag / C composite can then be used as a host material for lithium metal formation as described in the above-described synthesis embodiments. In the case of Example 1, in the presence of silver nanoparticles, the melt injection step of lithium metal within the carbon pores will be performed preferentially because the low eutectic melting point of the approximately 0.1w / w Li / Ag alloy occurs at a lower temperature than the lithium metal itself (i.e., 143°C relative to 180°C for pure lithium). When the low eutectic Li / Ag alloy reaches the lithium saturation point, it will precipitate solid lithium from the low eutectic melt, thereby guiding the formation of a large amount of lithium metal in the carbon pore structure where the silver nanoparticles initially remained. In another embodiment, as in the case of Example 3, the silver nanoparticles within the carbon pore structure can act as catalytic seed particles for the deposition and subsequent alloying of lithium metal from the lithium precursor gas during CVI.

[0272] Example 11. Reduction of lithium salts for synthesis of lithium carbon composites. One embodiment wherein lithium is generated within the pores of a porous carbon scaffold by mixing porous carbon particles with a lithium salt (e.g., LiF, LiCl, LiNO3, Li2CO3, LiI, LiBr, LiAlH4, LiOH, Li2O, LiO2, Li3N, etc.) at elevated temperature in the presence or absence of a reducing agent (e.g., H2, NaBH4, oxalic acid, glucose, carbon, etc.) to decompose the salt into lithium metal. The lithium salt may be pre-dissolved in a solvent (e.g., tetrahydrofuran, propylene carbonate, acetone, etc.) to more easily flow / absorb into the nanopores of the porous carbon scaffold. The reduction temperature and treatment time can vary, for example, the temperature can be 0°C to 900°C, for example, 0°C to 250°C, for example, 250°C to 300°C, for example, 300°C to 350°C, for example, 300°C to 400°C, for example, 350°C to 450°C, for example, 350°C to 400°C, for example, 400°C to 500°C, for example, 500°C to 600°C, for example, 600°C to 700°C, for example, 700°C to 800°C, for example, 800°C to 900°C, for example, 600°C to 1100°C. The solvent / salt mixture can contain 0.1% to 1% of the lithium salt and the remaining liquid solvent. Alternatively, the solvent / salt mixture can contain 1% to 10% of the lithium salt and the remaining liquid solvent. Alternatively, the solvent / salt mixture can contain 10% to 20% of the lithium salt and the remaining liquid solvent. Alternatively, the solvent / salt mixture may comprise 20% to 50% lithium salt and the remainder liquid solvent. Alternatively, the solvent / salt mixture may comprise greater than 50% lithium salt and the remainder liquid solvent. Alternatively, the solvent / salt may be substantially 100% lithium salt. The pressure of the reduction process may vary. In some embodiments, the pressure is atmospheric pressure. In some embodiments, the pressure is below atmospheric pressure. In some embodiments, the pressure is above atmospheric pressure.

[0273] Example 12. Electrochemical method for forming lithium carbon composites. In one embodiment, the lithium carbon composite can be synthesized by an electroplating mechanism, wherein an electrolytic cell is assembled with a porous carbon working electrode (prepared by slurry casting on a copper foil or nickel sheet collector) and a lithium metal counter electrode separated from each other in a liquid electrolyte comprising a lithium salt (e.g., LiPF6, LiFSI, LiTFSI, LiCl, LiBr, LiI, LiNO3, etc.) and an anhydrous organic solvent (e.g., propylene carbonate, ethylene carbonate, 1,3-dioxolane, 1,2-dimethoxyethane, tetrahydrofuran, acetonitrile, etc.). A negative bias voltage (e.g., -1V, -2V, -3V, -4V, -5V, -6V, etc.) is applied to promote Li+ reduction in the porous carbon electrode. The amount of charge transferred (Ah) is used to track the Li metal load, and the applied voltage is then stopped once the desired Li load is reached. The lithium-carbon electrode can then be transferred to a Li ion battery and used as an anode.

[0274] An embodiment similar to the above, in which the porous carbon electrode is prepared on a roll-to-roll coater, which is then conveyed to an electrolytic cell (as described above) contained in an inert atmosphere, in which a negative bias voltage is applied as described in the above embodiment, and lithium plating is performed while the electrode is continuously moving on the roller. Therefore, the degree of lithium metal loading is determined by the conveying speed of the roll-to-roll device. In addition, the electrolytic cell may include a dissolved polymer (e.g., polyacrylonitrile, polyvinylidene fluoride, polydopamine, etc.) so that when the electrode leaves the tank and is subsequently dried, the polymer film remains on the electrode surface, acting as a barrier to the atmosphere, thereby minimizing the oxidation of the lithium metal formed in the porous carbon.

[0275] In another more preferred embodiment, lithium plating can be performed in situ in an assembled Li-ion cell, wherein the porous carbon electrode (described above) is the anode and conventional Li-containing transition metal oxides known in the art (e.g., LiFePO4, LiCoO2, NCA, NMC111, NMC532, NMC622, etc.) are used as cathodes. Lithium plating occurs when the cell is charged to its 100% charged operating voltage (e.g., 4.2V). In this "anode-free" structure, the Li+ source is the cathode. When the cell is discharged, the process is reversed (Li+ is stripped from the porous carbon electrode). This embodiment is preferred because it does not require handling of active lithium metal in an environment external to the cell, and because the cathode serves as the sole source of Li+ in the system, the energy density of the cell can be improved.

[0276] Example 13. End coating method of lithium carbon composite. Due to the high reactivity of lithium metal under atmospheric conditions (e.g., oxidation reactions with water, oxygen and carbon dioxide), it may be necessary to coat / protect the surface of lithium using the end coating method described herein. In one embodiment, after the synthesis of LCC as described in Examples 1 to 6, the composite is then heated to a certain temperature (e.g., 400°C to 1000°C) to promote the decomposition of hydrocarbon gases (e.g., acetylene, propylene, ethylene, methane, propane, propadiene / propyne, etc.). At the peak temperature, the hydrocarbon gas is introduced into a heating chamber including the LCC material, and a chemical vapor deposition reaction is allowed to deposit carbon on the surface of the LCC material according to the reaction equation CxHy->C+H2. The thickness of the coating can be controlled by the residence time (e.g., 0.1 hours to 6 hours) of the hydrocarbon gas. The application of the carbon coating will then protect the silicon from oxidation under atmospheric conditions. In another embodiment, the LCC material can be coated with a polymer (eg, polydopamine, polyacrylonitrile, polyaniline, polypyrrole, etc.) to allow for lower temperature (eg, <200° C.) processing.

[0277] Example 14. Surface functionality methods and metrics. The surface functionality of the composite materials comprising carbon and lithium of the present disclosure can be changed to obtain desired electrochemical properties. One such property of the composite material of the particles is the concentration of atomic species at the surface of the composite material relative to the interior of the composite material. This difference in the concentration of atomic species at the surface of the composite material of the particles relative to the interior can be determined as known in the art, such as by x-ray photoelectron spectroscopy (XPS). For example, the concentration of Li:C at the surface (defined as the end 5nm of the surface of the particle) can be determined by this method. In some embodiments, the ratio of Li:C at the surface is about 0.1:1 to 10:1. In certain embodiments, the ratio of Li:C at the surface is about 0:1. In other embodiments, the ratio of Li:C at the surface is about 1:0. In another example, the ratio of Li:O at the surface is about 0:1 to 1:0.

[0278] Another property that can predict surface functionality is the pH of the LCC composite. Composites of the present disclosure include pH values ​​of less than 1 to about 14, such as less than 5, 5 to 8, or greater than 8. In some embodiments, the pH of the composite is less than 4, less than 3, less than 2, or even less than 1. In other embodiments, the pH of the composite is about 5 to 6, about 6 to 7, about 7 to 8, or 8 to 9, or 9 to 10. In other embodiments, the pH of the composite is high and the pH range is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.

[0279] Other methods and metrics for determining carbon structure include X-ray diffraction (XRD) and Raman spectroscopy. With respect to XRD, the graphitic properties of carbon materials can be evaluated by monitoring the peak intensities at various 2q corresponding to various Miller indices. Without being bound by theory, the diffraction lines of graphite are classified into various groups, such as indices of 001, hk0, and hk1, primarily because of the strong anisotropy in the structure. One such category is 002, corresponding to the basal plane of graphite, which is located at 2θ to 26°; this peak is prominent in highly graphitized carbon materials. Carbon materials with lesser degrees of graphitic properties and small grain sizes may be characterized by very broad 001 lines (e.g., 002) and offsets (e.g., 2θ to 23°), as well as asymmetric hk lines (e.g., 10 corresponds to 2θ to 43°) due to the lower degree of stacking layers. In addition, the Scherrer formula can be used to calculate the grain size (Lc) from the 002 line and the grain size (La) from the 100 line.

[0280] About Raman spectrum, this method can also be used to evaluate the graphitic properties of carbon reported in the art. The position, shape and size of Raman D and G bands are known in the art, for calculating La values ​​by Tuinstra Koenig (TK) model for >2nm particle size, or when TK model calculates <2nm particle size by Ferrari (FR) model to calculate La values ​​(Ferrari, AC, & Robertson, J. (1970); Tuinstra, F., & Koening, JL (1970). Raman spectrum of graphite. The Journal of Chemical Physics, 53 (3), 1126-1130). Interpretation of Raman spectra of disordered and amorphous carbon. Physical Review B, 61 (20), 14095-14107). These models provide a measure of disorder in carbon materials and represent the length of graphene crystal sheets in carbon materials.

[0281] Another analytical method is to use an inert gas fusion instrument to measure oxygen, nitrogen and hydrogen. Lithium-carbon composite materials can contain different amounts of carbon, oxygen, hydrogen and nitrogen, which are measured by an inert gas fusion instrument (LECO ONH 836) known in the art. The lithium-carbon composite sample is rapidly heated to about 3000 ° C in a graphite arc furnace under flowing helium. The oxygen in the sample is carbon-thermally reduced to CO2 and / or CO, which is entrained in the helium gas flow and quantified downstream using an IR spectrometer. Hydrogen is precipitated from the sample in the form of H2, which is catalytically converted into H2O in the gas phase, and is also quantified using an IR spectrometer. Finally, nitrogen is precipitated from the sample in the form of N2, and is quantified using a thermal conductivity detector.

[0282] In some embodiments, the lithium-carbon composite material comprises a nitrogen content of 0 to 90%, such as 0.1% to 1%, such as 1% to 3%, such as 1% to 5%, such as 1% to 10%, such as 10% to 20%, such as 20% to 30%, such as 30% to 90%. In some embodiments, the oxygen content is 0 to 90%, such as 0.1% to 1%, such as 1% to 3%, such as 1% to 5%, such as 1% to 10%, such as 10% to 20%, such as 20% to 30%, such as 30% to 90%.

[0283] Example 15. Stability of lithium-carbon composites under ambient conditions. The instability of lithium metal under ambient conditions is well known in the art. The present disclosure provides lithium protected within a porous carbon scaffold having an optional end coating applied to the composite particles. This protection can be described by the confinement of the lithium within the carbon scaffold and is manifested as reduced or eliminated reactivity in air (oxygen), stability in contact with other battery components (chemistry), stability in operation (electrochemistry), and inhibition of dendrites when the battery is cycled. For example, a measure of reaction with organic solvents, such as the onset time or severity, can be measured by H2 release and / or total amount. Alternatively, the onset time or severity of rust / discoloration / oxidation of lithium-carbon in air can be measured. Alternatively, stability can be assessed by TGA / DSC by measuring mass absorption due to oxidation of lithium within the composite. In addition, DSC is also known to provide information about the melting point of lithium, changes in which produce information about the stability and / or arrangement of lithium within the porosity of the carbon scaffold. Alternatively, the stability of the half-cell relative to lithium metal can be measured to determine the number of galvanostatic cycles until dendrite failure (i.e., short circuit of the half-cell). Alternatively, the stability can be assessed by small angle X-ray scattering (SAXS) or neutron scattering to determine the distribution and size of the lithium in the pores of the porous carbon.

[0284] Example 16. Solution intrusion method for preparing lithium-silicon alloy-carbon composite materials. In an exemplary solution intrusion method, 0.2 grams of Li metal is dissolved in a 1 molar solution containing 3.66 grams of naphthalene and 28.6 mL of tetrahydrofuran (THF) by vigorous stirring under an inert (argon) atmosphere until a dark green translucent solution is obtained. Then 1.0 grams of silicon-carbon composite is added to 28.6 mL of Li-naphthalene / THF solution and soaked for 15 minutes. Lithiation is carried out by a chemical reaction in which lithium is alloyed with silicon alone, embedded with carbon, and the oxide component of the silicon-carbon composite is converted. After soaking, the lithium alloyed silicon-carbon composite is collected after five centrifugation / rinsing steps using anhydrous THF, and then dried under vacuum.

[0285] exist Figure 1 The X-ray diffraction spectra of the as-received silicon-carbon composite and the lithium-alloyed silicon-carbon composite are depicted in Figure 2. Both spectra were collected in an argon-filled glove box without exposure to air by covering with Kapton tape. The pure silicon-carbon composite shows characteristic spectra of amorphous silicon and carbon. The lithium-alloyed silicon-carbon composite remains amorphous with only a slight increase in intensity in the region of 2θ of 20 and 45. This indicates that no inactive crystalline lithium phases, such as lithium hydroxide, lithium oxide or lithium carbonate, are formed as a result of the solution intrusion process.

[0286] In order to understand the oxidation behavior of the lithium alloyed silicon-carbon composite under ambient atmosphere, the subsequent XRD analysis was performed without using Kapton tape. Figure 2 The results depicted in show very little change after only about 40 minutes of exposure to the atmosphere, but after about 24 hours in the atmosphere crystalline lithium carbonate is evident (ICDD PDF#009-0359).

[0287] The elemental composition of the silicon-carbon composite and lithium-alloyed silicon-carbon composite was analyzed via X-ray photoelectron spectroscopy (XPS) shown in Table 6. Due to the nature of the technique, the samples were exposed to air before analysis, and the elemental composition only represents about 10 nanometers of the material surface. The pure silicon-carbon composite exhibits characteristic amounts of silicon, carbon, and oxygen, while the lithium-alloyed silicon-carbon composite exhibits a high lithium atomic fraction and a corresponding low silicon signal, indicating that significant oxide film formation occurs upon exposure to air, resulting in dealloying of lithium and subsequent formation of LixOyCz moieties (e.g., LiOH, Li2O, Li2CO3).

[0288] Table 6. X-ray photoelectron spectroscopy results of pure silicon-carbon composites and lithium-alloyed silicon-carbon composites.

[0289]

[0290] Example 17. Electrochemical testing of electrodes treated via solution intrusion to produce lithium-silicon alloy-carbon composites. The electrodes of the silicon-carbon composites were prepared as aqueous slurries having a weight composition of 80:10:10 consisting of silicon-carbon composites, Super C45 as a conductive additive, and sodium polyacrylate (Na-PAA) as a binder, respectively. The slurry was coated on a copper foil as a current collector and then dried at 80°C for about 30 minutes, then vacuum dried at 120°C for about 2 hours, and then transferred to an argon-filled glove box for battery assembly.

[0291] Electrodes with a diameter of about 0.5 inches were punched out from the coated sheets and subsequently soaked in a 1M solution of Li-biphenyl in THF for 30 minutes to allow lithium alloying via solution intrusion. The lithium alloyed silicon-carbon composite electrode was recovered from the solution and rinsed with pure THF to remove the residual Li-biphenyl component and then dried at ambient temperature (about 27°C) under an inert atmosphere. Celgard 2325 three-layer polyethylene / polypropylene / polyethylene was used as a separator, Li metal foil was used as a counter electrode, and 1M LiPF6 in 2:1 w / w of ethylene carbonate: diethyl carbonate with 10wt% fluoroethylene carbonate was used as the base electrolyte, and the lithium alloyed silicon-carbon composite electrode was assembled into a CR2032 half-cell. The half-cell was tested on a current / potentiostat, where the cell was allowed to stand for 6 hours at an open circuit voltage (OCV) and the measured voltage was 0.573V (relative to Li / Li+). Then, it was discharged (lithiation) to 0.005 V (relative to Li / Li+) at a constant current (constant current) rate of about 150 mAh / g (C / 10), followed by charging (delithiation) to 1.5 V (relative to Li / Li+) at the same constant current, constituting one cycle. The first cycle efficiency (FCE) and gravimetric capacity were determined from this cycle, and the results are depicted in Table 2. Two more C / 10 discharge / charge cycles were performed, followed by seven cycles at 300 mAh / g (C / 5).

[0292] Figure 3 The cycling stability performance of silicon-carbon composites and two lithium-alloyed silicon-carbon composites prepared using variations of the method outlined in Example 17 is shown. The lithium alloying mechanism can improve the cycle-to-cycle Coulombic efficiency and capacity retention. Table 7 summarizes the synthesis conditions and electrochemical test results for a series of lithium-alloyed silicon-carbon composites prepared according to Example 17. For these samples, except for samples 17-C1 and C2 (controls that were not subjected to the infiltration process), the lithium salt was lithium naphthalene or lithium biphenyl, the infiltration temperature was 25°C to 40°C, and the carrier solvent was dimethoxymethane or tetrahydrofuran.

[0293] Table 7. Synthesis conditions and electrochemical properties of lithium alloyed silicon-carbon composites prepared in electrode form.

[0294]

[0295] TBD = To be determined; PAA = polyacrylic acid; SBR = styrene-butadiene rubber, CMC = carboxymethyl cellulose; PVdF = polyvinylidene fluoride

[0296] Specific embodiments Embodiment 1. A granular material comprising a plurality of composite particles, wherein the composite particles comprise: (i) a porous carbon skeleton; (ii) a plurality of nanoscale amorphous elemental silicon domains located within the micropores and / or mesopores of the porous carbon skeleton; and (iii) a plurality of lithium domains, including lithium-silicon alloy domains, non-silicon alloy domains, or a combination thereof.

[0297] Embodiment 2. The composite according to embodiment 1, wherein the porous carbon skeleton comprises no less than 0.5 cm 3 / g pore volume, DPv80 no greater than 2nm, DPv99 no greater than 50nm, and Dv50 of 0.1 micron to 50 microns.

[0298] Embodiment 2. The composite according to embodiment 1, wherein the porous carbon skeleton comprises no less than 0.5 cm 3 / g of pore volume, DPv70 no greater than 2nm, DPv90 no greater than 50nm, and Dv50 of 0.1 micron to 50 microns.

[0299] Embodiment 3. The composite according to embodiment 1, wherein the porous carbon skeleton comprises no less than 0.5 cm 3 / g pore volume, DPv80 no greater than 2nm, DPv99 no greater than 50nm, and Dv50 of 0.1 micron to 50 microns.

[0300] Embodiment 4. The composite according to any one of embodiments 1 to 3, wherein the porous carbon skeleton comprises no less than 0.6 cm 3 / g pore volume.

[0301] Embodiment 5. The composite according to any one of embodiments 1 to 4, wherein the silicon content is 30% to 70% and the lithium content is 0.1% to 20%.

[0302] Embodiment 6. The composite according to any one of embodiments 1 to 5, wherein the particle shape is spherical.

[0303] Embodiment 7. The composite according to any one of embodiments 1 to 6, wherein the particle size distribution comprises two or more modes.

[0304] Embodiment 8. The composite according to any one of embodiments 1 to 7, wherein the composite particle size distribution comprises a plurality of modes.

[0305] Embodiment 9. The composite according to any one of embodiments 1 to 8, wherein the composite particle size distribution comprises a left skewness.

[0306] Embodiment 10. The composite according to any one of embodiments 1 to 8, wherein the composite particle size distribution comprises a right skewness.

[0307] Embodiment 11. A composite according to any one of embodiments 1 to 10, wherein the surface of the composite particles is coated with an amorphous carbon layer, for example via chemical vapor deposition of hydrocarbons (e.g., acetylene, propylene, methane, propane, ethylene, and combinations thereof).

[0308] Embodiment 12. The composite according to any one of embodiments 1 to 10, wherein the surface of the composite particles is passivated via chemical vapor passivation with hydrocarbons (eg, acetylene, propylene, methane, propane, ethylene, and combinations thereof).

[0309] Embodiment 13. A composite according to any one of embodiments 1 to 10, wherein the surface of the composite particles is coated with an organic polymer layer, such as polydopamine, polyacrylonitrile, polyethylene glycol, polyvinylidene fluoride, polyaniline, polyacrylic acid, polysulfide and combinations thereof.

[0310] Embodiment 12. A composite according to any one of embodiments 1 to 10, wherein a metal oxide (Al2O3, TiO2, ZrO2, Li2O, ZnO, SiO2 and combinations thereof) is coated on the surface of the composite particles using vapor phase atomic layer deposition (ALD).

[0311] Embodiment 13. A composite according to any one of embodiments 1 to 10, wherein a metal oxide, such as B2O3, Al2O3, LiAlO2, TiO2, Li2ZrO3, ZrO2, Li2O, ZnO, SiO2, LiNbO3, Li2WO4, and combinations thereof, is coated on the surface of the composite particles using a liquid phase sol-gel process.

[0312] Embodiment 14. The composite according to any one of embodiments 1 to 13, wherein the composite comprises a capacity greater than 900 mAh / g.

[0313] Embodiment 15. The composite according to any one of embodiments 1 to 13, wherein the composite comprises a capacity greater than 1300 mAh / g.

[0314] Embodiment 16. The composite according to any one of embodiments 1 to 13, wherein the composite comprises a capacity greater than 1600 mAh / g.

[0315] Embodiment 17. The composite according to any one of embodiments 1 to 16, wherein the composite comprises an average coulombic efficiency of >0.9970 measured in a half-cell at a C / 10 rate cycled from 5 mV to 0.8 V in a cycle range from cycle 7 to cycle 20. Embodiment 18. The composite according to any one of embodiments 1 to 16, wherein the composite comprises an average coulombic efficiency of >0.9980 measured in a half-cell at a C / 10 rate cycled from 5 mV to 0.8 V in a cycle range from cycle 7 to cycle 20. Embodiment 19. The composite according to any one of embodiments 1 to 16, wherein the composite comprises an average coulombic efficiency of >0.9985 measured in a half-cell at a C / 10 rate cycled from 5 mV to 0.8 V in a cycle range from cycle 7 to cycle 20. Embodiment 20. The composite according to any one of embodiments 1 to 16, wherein the composite comprises an average coulombic efficiency of >0.9990 measured in a half-cell at a C / 10 rate cycled from 5 mV to 0.8 V in a cycle range from cycle 7 to cycle 20. Embodiment 21. The composite according to any one of embodiments 1 to 16, wherein the composite comprises an average coulombic efficiency of >0.9995 measured in a half-cell at a C / 10 rate cycled from 5 mV to 0.8 V in a cycle range from cycle 7 to cycle 20. Embodiment 22. The composite according to any one of embodiments 1 to 16, wherein the composite comprises an average coulombic efficiency of >0.9999 measured in a half-cell at a C / 10 rate cycled from 5 mV to 0.8 V in a cycle range from cycle 7 to cycle 20. Embodiment 23. The composite according to any one of embodiments 1 to 22, wherein Z is less than 10.

[0316] Embodiment 24. A silicon-carbon composite comprising: (i) a porous carbon scaffold comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g; (ii) a silicon content of 30% to 70%; and (iii) a surface coating at least partially applied to form a surface coating on a surface area of ​​the silicon-carbon composite, the surface coating comprising at least one or more elements of B, C, Si, Li, Al, Ti, Zr, Nb and W.

[0317] Embodiment 25. The silicon-carbon composite material according to Embodiment 24, wherein the surface coating has a thickness of 0.1 nm to 1000 nm.

[0318] Embodiment 26. The silicon-carbon composite material of Embodiment 24 or Embodiment 25, wherein the surface coating comprises a metal oxide.

[0319] Embodiment 27. The silicon-carbon composite material according to any one of Embodiments 24 to 26, wherein the surface coating region covers at least 50% of the surface area of ​​the silicon-carbon composite.

[0320] Embodiment 28. The silicon-carbon composite material according to any one of Embodiments 24 to 27, wherein the silicon-carbon composite material includes an additional coating on the surface coating, so that the surface coating and the additional coating form a surface coating region.

[0321] Embodiment 29. A silicon-carbon composite material according to Embodiment 28, wherein the additional coating is a carbon coating.

[0322] Embodiment 30. The silicon-carbon composite material according to any one of Embodiments 24 to 29, wherein the surface area of ​​the silicon-carbon composite is less than 30 m 2 / g.

[0323] Embodiment 31. A silicon-carbon composite material according to any one of Embodiments 24 to 29, wherein the surface area of ​​the silicon-carbon composite is less than 20 m 2 / g.

[0324] Embodiment 32. A method for making a composite material comprising a plurality of particles, the method comprising:

[0325] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0326] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0327] c. heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon-carbon composite.

[0328] Embodiment 33. A method for making a composite material comprising a plurality of particles, the method comprising:

[0329] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0330] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0331] c. heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon alloy-carbon composite.

[0332] Embodiment 34. A method for making a composite material comprising a plurality of particles, the method comprising:

[0333] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0334] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0335] c. Heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon alloy silicon-carbon composite, wherein the lithium also includes non-silicon-alloy domains.

[0336] Embodiment 35. A method for making a composite material comprising a plurality of particles, the method comprising:

[0337] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0338] b. heating the carbon framework in the presence of a lithium-containing precursor to produce a lithium-carbon composite;

[0339] c. Heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite material.

[0340] Embodiment 36. A method for making a composite material comprising a plurality of particles, the method comprising:

[0341] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0342] b. heating the carbon framework in the presence of a lithium-containing precursor to produce a lithium-carbon composite;

[0343] c. Heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon alloy-carbon composite.

[0344] Embodiment 37. A method for making a composite material comprising a plurality of particles, the method comprising:

[0345] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0346] b. heating the carbon framework in the presence of a lithium-containing precursor to produce a lithium-carbon composite;

[0347] c. Heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon alloy-carbon composite material wherein the lithium also includes non-silicon-alloy domains.

[0348] Embodiment 38. The method for making a composite material comprising a plurality of particles according to any one of Embodiments 32 to 37, wherein the lithium-containing precursor is introduced in the form of a gas.

[0349] Embodiment 39. A method for manufacturing a composite material comprising a plurality of particles according to any one of Embodiments 32 to 37, wherein a lithium-containing precursor is introduced in the form of a solid or a liquid and is converted into a gaseous form under conditions for an alloying process.

[0350] Embodiment 40. The method for making a composite material comprising a plurality of particles according to Embodiment 39, wherein the gasified lithium-containing precursor is mixed with an inert gas.

[0351] Embodiment 41. The method for producing a composite material comprising a plurality of particles according to embodiment 40, wherein the inert gas comprises nitrogen, argon, hydrogen, or a combination thereof.

[0352] Embodiment 42. A method for producing a composite material comprising a plurality of particles according to any one of embodiments 32 to 37, wherein the temperature of introducing lithium is 100° C. to 1700° C. Embodiment 43. A method for producing a composite material comprising a plurality of particles according to any one of embodiments 32 to 37, wherein the lithium precursor is lithium and the temperature is at least 1330° C.

[0353] Embodiment 44. A method for producing a composite material comprising a plurality of particles according to any one of Embodiments 32 to 37, wherein the lithium precursor is heated to a temperature corresponding at least to the boiling point.

[0354] Embodiment 45. A method for manufacturing a composite material comprising multiple particles according to Embodiment 44, wherein the lithium precursor is lithium bis(trimethylsilyl)amide, lithium acetylsalicylate, lithium amide, lithium bromide, lithium borohydride, lithium chloride, lithium hydride, lithium hydroxide or a combination thereof.

[0355] Embodiment 46. A method for making a composite material comprising a plurality of particles according to any one of Embodiments 32 to 37, wherein the silicon CVI process is followed by a lithium CVI process. Embodiment 47. A method for making a composite material comprising a plurality of particles according to any one of Embodiments 32 to 37, wherein silicon and lithium are introduced simultaneously according to a co-CVI process. Embodiment 48. A method for making a composite material comprising a plurality of particles according to any one of Embodiments 32 to 47, wherein the conversion of the lithium-containing precursor to lithium can be achieved by various methods such as chemical reduction or electrochemical reduction.

[0356] Embodiment 49. A method for making a composite material comprising a plurality of particles, the method comprising:

[0357] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0358] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0359] c. Melting a lithium precursor in the presence of a silicon-carbon composite to produce a lithium-silicon-carbon composite.

[0360] Embodiment 50. A method for making a composite material comprising a plurality of particles, the method comprising:

[0361] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0362] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0363] c. Melting a lithium precursor in the presence of a silicon-carbon composite to produce a lithium-silicon alloy-carbon composite.

[0364] Embodiment 51. A method for making a composite material comprising a plurality of particles, the method comprising:

[0365] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0366] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0367] c. Melting a lithium precursor in the presence of a silicon-carbon composite to produce a lithium-silicon alloy-carbon composite, wherein the lithium also includes non-silicon-alloy domains.

[0368] Embodiment 52. A method for making a composite material comprising a plurality of particles, the method comprising:

[0369] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0370] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas and a lithium precursor, wherein the elevated temperature is above the melting point of the lithium precursor to impregnate silicon and lithium into one or more pores of the porous carbon framework; and

[0371] c. Wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

[0372] Embodiment 53. A method for making a composite material comprising a plurality of particles, the method comprising:

[0373] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0374] b. melting a lithium precursor in the presence of a carbon skeleton material to produce a lithium-silicon composite material;

[0375] c. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite; and

[0376] d. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof. Embodiment 54. A method for making a composite material comprising a plurality of particles according to any one of Embodiments 49 to 53, wherein the temperature at which melt intrusion is achieved is 25°C to 1000°C.

[0377] Embodiment 55. A method for producing a composite material comprising a plurality of particles according to any one of Embodiments 49 to 53, wherein the temperature at which lithium intrusion is achieved is at least the melting point of the lithium precursor.

[0378] Embodiment 56. A method for producing a composite material comprising a plurality of particles according to Embodiment 55, wherein the lithium precursor is lithium metal.

[0379] Embodiment 57. A method for manufacturing a composite material comprising multiple particles according to any one of Embodiments 49 to 53, wherein the lithium precursor is lithium carbonate, lithium acetate, lithium amide, lithium bromide, lithium borohydride, lithium peroxide, lithium chloride, lithium fluoride, lithium hydride, lithium hydroxide, lithium hydrogen sulfate, lithium dihydrogen phosphate, lithium nitrate, lithium phosphate, lithium nitride, lithium sulfate, lithium sulfide, lithium disulfide, lithium sulfite, lithium aluminum alloy, lithium aluminum copper alloy, lithium tin alloy, lithium silicon alloy or a combination thereof.

[0380] Embodiment 58. A method for producing a composite material comprising a plurality of particles according to any one of Embodiments 49 to 53, wherein the conversion of the lithium-containing precursor to lithium is achieved by chemical reduction or electrochemical reduction.

[0381] Embodiment 59. A method for manufacturing a composite material comprising a plurality of particles according to Embodiment 58, wherein the reducing agent is a hydride reagent, dihydride, lithium aluminum hydride, borohydride, sodium borohydride, diborane, an organometallic reagent, a Grignard reagent, a dialkylcopperlithium reagent, or a combination thereof.

[0382] Embodiment 60. A method for making a composite material comprising a plurality of particles, the method comprising:

[0383] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0384] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material;

[0385] c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; and

[0386] d. Reducing the lithium precursor to produce a lithium-silicon-carbon composite material.

[0387] Embodiment 61. A method for making a composite material comprising a plurality of particles, the method comprising:

[0388] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0389] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; and

[0390] c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; and

[0391] d. Reducing the lithium precursor to produce a lithium-silicon alloy-carbon composite material.

[0392] Embodiment 62. A method for making a composite material comprising a plurality of particles, the method comprising:

[0393] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0394] b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material;

[0395] c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; and

[0396] d. Reducing the lithium precursor to produce a lithium-silicon alloy-carbon composite material, wherein the lithium also includes non-silicon-alloy domains.

[0397] Embodiment 63. A method for making a composite material comprising a plurality of particles, the method comprising:

[0398] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0399] b. contacting the porous carbon framework with a solution or suspension of a lithium precursor to incorporate the lithium precursor into one or more pores of the porous carbon framework;

[0400] c. reducing a lithium precursor to produce a lithium-carbon composite;

[0401] d. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite; and

[0402] e. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

[0403] Embodiment 64. A method for making a composite material comprising a plurality of particles, the method comprising:

[0404] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0405] b. contacting the porous carbon framework with a solution or suspension of a lithium precursor to incorporate the lithium precursor into one or more pores of the porous carbon framework;

[0406] c. heating the carbon skeleton containing a lithium precursor at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon skeleton, thereby providing a lithium-silicon-carbon composite material;

[0407] as well as

[0408] d. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof. Embodiment 65. A method for making a composite material comprising a plurality of particles according to any one of Embodiments 60 to 64, wherein the lithium precursor is lithium carbonate, lithium acetate, lithium amide, lithium bromide, lithium borohydride, lithium peroxide, lithium chloride, lithium fluoride, lithium hydride, lithium hydroxide, lithium hydrogen sulfate, lithium dihydrogen phosphate, lithium nitrate, lithium phosphate, lithium nitride, lithium sulfate, lithium sulfide, lithium disulfide, lithium sulfite, lithium aluminum alloy, lithium aluminum copper alloy, lithium tin alloy, lithium silicon alloy, or a combination thereof.

[0409] Embodiment 66. A method for producing a composite material comprising a plurality of particles according to any one of Embodiments 60 to 65, wherein the conversion of the lithium-containing precursor to lithium is achieved by chemical reduction or electrochemical reduction.

[0410] Embodiment 67. A method for manufacturing a composite material comprising multiple particles according to Embodiment 66, wherein the reducing agent is a hydride reagent, dihydride, lithium aluminum hydride, borohydride, sodium borohydride, diborane, an organometallic reagent, a Grignard reagent, a dialkyl copper lithium reagent or a combination thereof.

[0411] Embodiment 68. An anode electrode comprising the lithium-silicon alloy-carbon composite material of any one of Embodiments 1 to 31.

[0412] Embodiment 69. An anode electrode comprising a lithium-silicon alloy-carbon composite material according to Embodiment 68, further comprising a specific carbon material and a binder.

[0413] Embodiment 70. An anode electrode comprising a lithium-silicon alloy-carbon composite material according to Embodiment 69, wherein the carbon material comprises graphite, graphene, carbon conductive additives such as Super C45, Super P, Ketjen Black, carbon nanotubes, carbon nanostructures and combinations thereof.

[0414] Embodiment 71. A method of producing an anode, comprising:

[0415] a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns;

[0416] b. mixing the mixture with a binder solution to form an electrode paste;

[0417] c. applying the electrode paste to the conductor, thereby producing the electrode;

[0418] d. Dry the electrode at a temperature below 180°C.

[0419] Embodiment 72. An electrochemical storage device comprising the electrode of any one of Embodiments 68 to 70.

[0420] Embodiment 73. The electrochemical storage device of Embodiment 72, wherein the cathode to anode pairing is less than 1.05 and the first cycle efficiency is greater than 85%.

[0421] From the foregoing it will be appreciated that, although specific embodiments of the disclosure have been described herein for purposes of illustration, various modifications may be made without deviating from the spirit and scope of the disclosure.

[0422] The various embodiments described above can be combined to provide additional embodiments. All U.S. patents, U.S. patent application publications, U.S. patent applications, foreign patents, foreign patent applications, and non-patent publications mentioned in this specification and / or listed in the application data sheet are incorporated herein by reference in their entirety. If necessary, various aspects of the embodiments can be modified to provide additional embodiments using the concepts of various patents, applications, and publications.

[0423] This application claims priority to U.S. Provisional Patent Application No. 63 / 337,526, filed on May 2, 2022, which is incorporated herein by reference in its entirety.

[0424] These and other changes can be made to the embodiments in light of the above detailed description. Generally, in the above claims, the terms used should not be interpreted as limiting the claims to the specific embodiments disclosed in the specification and claims, but should be interpreted to include all possible embodiments and the full range of equivalents authorized by these claims. Therefore, the claims are not limited by the present disclosure.

Claims

1. A particulate material comprising a plurality of lithium-silicon-carbon composite particles, wherein the composite particles comprise: (i) porous carbon framework; (ii) a plurality of nanoscale amorphous elemental silicon domains located within the micropores and / or mesopores of the porous carbon framework; and (iii) a plurality of lithium domains, including lithium-silicon alloy domains, non-silicon alloy domains, or a combination thereof.

2. The lithium-silicon-carbon composite according to claim 1, wherein the porous carbon support comprises more than 0.5 cm 3 / g pore volume.

3. The lithium-silicon-carbon composite of claim 1, further comprising a plurality of particles comprising a Dv50 of 0.1 microns to 50 microns.

4. The lithium-silicon-carbon composite according to any one of claims 1 to 3, further comprising less than 30 m 2 / g of surface area.

5. The lithium-silicon-carbon composite according to claim 1, further comprising greater than 900 m 2 / g capacity.

6. An electrode comprising the lithium-silicon-carbon composite according to any one of claims 1 to 5.

7. The electrode according to claim 6, wherein the at least one binder material is selected from styrene-butadiene rubber sodium carboxymethylcellulose (SBR-Na-CMC), polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA) and combinations thereof.

8. The electrode according to claim 6, wherein the at least one carbon material is selected from graphite, graphene, carbon conductive additives such as Super C45, Super P, Ketjen Black, carbon nanotubes, carbon nanostructures and combinations thereof.

9. A lithium-silicon battery comprising the lithium-silicon-carbon composite according to any one of claims 1 to 5.

10. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; as well as c. heating the silicon-carbon composite in the presence of a lithium-containing precursor to produce a lithium-silicon-carbon composite, wherein the lithium comprises silicon-alloy domains, non-silicon-alloy domains, or a combination thereof.

11. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. heating the carbon skeleton in the presence of a lithium-containing precursor to produce a lithium-carbon composite; c. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon alloy-carbon composite material, wherein the lithium includes silicon-alloy domains, non-silicon-alloy domains, or a combination thereof.

12. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; as well as c. melting a lithium precursor in the presence of the silicon-carbon composite to produce a lithium-silicon-carbon composite, wherein the lithium comprises silicon-alloy domains, non-silicon-alloy domains, or a combination thereof.

13. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas and a lithium precursor, wherein the elevated temperature is above the melting point of the lithium precursor to impregnate both silicon and lithium into one or more pores of the porous carbon framework; and c. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

14. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. melting a lithium precursor in the presence of the carbon skeleton material to produce a lithium-silicon composite material; c. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite material; as well as d. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

15. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. heating the porous carbon framework at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a silicon-carbon composite material; c. contacting the silicon-carbon composite with a solution or suspension of a lithium precursor to incorporate the lithium precursor into the silicon-carbon composite via intrusion of the solution or suspension; as well as d. reducing the lithium precursor to produce a lithium-silicon-carbon composite material, wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

16. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. contacting the porous carbon framework with a solution or suspension of a lithium precursor to incorporate the lithium precursor into one or more pores of the porous carbon framework; c. reducing the lithium precursor to produce a lithium-carbon composite; d. heating the lithium-carbon composite at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon framework, thereby providing a lithium-silicon-carbon composite material; and e. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

17. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon framework comprising micropores, mesopores, or both, wherein the porous carbon framework comprises particles having a Dv50 of 0.1 microns to 50 microns; b. contacting the porous carbon framework with a solution or suspension of a lithium precursor to incorporate the lithium precursor into one or more pores of the porous carbon framework; c. heating the carbon skeleton containing the lithium precursor at an elevated temperature in the presence of a silicon-containing gas to impregnate silicon into the pores of the porous carbon skeleton, thereby providing a lithium-silicon-carbon composite material; as well as d. wherein the lithium within the composite comprises lithium-silicon alloy domains, non-silicon-alloy domains, or a combination thereof.

18. A method for making a composite material comprising a plurality of particles, the method comprising: a. Providing a porous carbon scaffold having micropores and mesopores; b. introducing a compound comprising Si and Fe, Al, Ni, W or Ti into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form a metal-carbon composite; c. surface coating a surface region of the metal-carbon composite with a surface coating comprising aluminum oxide or zirconium oxide to form a surface-coated region on the surface region of the silicon-carbon composite, thereby forming a surface-coated silicon-carbon composite.

19. The lithium-silicon alloy-carbon composite according to any one of claims 1 to 5, further comprising a surface coating at least partially applied to form a surface coating on a surface area of ​​the composite, the surface coating comprising at least one or more elements of C, Si, Li, Al, Ti, Zr, Nb and W.

20. The lithium-silicon alloy-carbon composite of claims 18 to 19, further comprising a surface coating at least partially applied to form a surface coating on a surface region of the composite, the surface coating comprising an oxide comprising aluminum, zirconium, titanium, or a combination thereof.

21. The method for producing a lithium-silicon carbon composite material according to claim 18 to claim 19, wherein the surface coating is based on a gas vapor deposition method.

22. The method for producing a lithium-silicon carbon composite material according to claim 18 to claim 19, wherein the surface coating is based on: a. treating the composite material with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound, b. treating the treated compound with moisture or oxygen or ozone to form the surface coating.

23. The method for producing a lithium-silicon alloy-carbon composite material according to claim 18 to claim 19, wherein the coating of the surface coating region is performed at a temperature of 15°C to 450°C.

24. An anode electrode comprising lithium-silicon alloy-carbon composite particles, wherein the lithium-silicon alloy-carbon composite particles comprise: a. A porous carbon skeleton comprising a carbon skeleton having a diameter of not less than 0.5 cm 3 / g of total pore volume of micropores and mesopores; b.30% to 70% silicon content; c. a plurality of nanoscale amorphous elemental silicon domains located within the micropores and / or mesopores of the porous carbon framework; and d. Multiple lithium domains comprising lithium-silicon alloy.

25. The anode electrode according to claim 24 further includes a surface coating at least partially applied to form a surface coating area on the surface area of ​​the silicon-carbon composite, wherein the surface coating contains at least one or more elements of Li, B, Al, Si, P, Ti, Zr, Nb and W.

26. The anode electrode according to claim 25, wherein the surface coating has a thickness of 0.1 nm to 1 μm.

27. The anode electrode according to claim 24 to claim 26, wherein the surface coating comprises a metal oxide from at least one or more of the elements B, Al, Si, Zr and Li.

28. The anode electrode of claim 24 to claim 27, wherein the surface coating region covers at least 50% or more of the surface area of ​​the silicon-carbon composite.

29. The anode electrode according to any one of claims 24 to 28, wherein the composite material comprises a further coating on the surface coating, such that the surface coating and the further coating form the surface coating region.

30. The anode electrode of claim 29, wherein the further coating is a carbon coating.

31. A method for manufacturing an anode electrode according to any one of claims 24 to 30, comprising the steps of: a. mixing the lithium-silicon alloy-carbon composite with at least one carbon to produce a mixture; b. mixing the mixture with a binder solution to form an electrode paste; c. applying the electrode paste to a conductor, thereby producing at least one electrode, d. Drying the at least one electrode at a temperature below 180°C.

32. An electrochemical storage device, in particular an electrochemical storage device in the form of a lithium-silicon battery, comprising: a. at least one anode electrode according to any one of claims 24 to claim 30; b. at least one electrode formed as a cathode, comprising a transition metal oxide; c. a separator disposed between the cathode and the anode; and d. An electrolyte comprising lithium ions.

Citation Information

Patent Citations

  • Methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same

    US10590277B2

  • Methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same

    US10711140B2

  • Aluminum Nitride Synthesis from Nut Shells

    US20210045417A1

  • Device and method for filtering a fluid circulating in a plumbing and heating system

    US20210052995A1

  • Activated carbon cryogels and related methods

    US7723262B2